Lithium-ion secondary battery
By adding magnesium and fluorine to the positive electrode active substance of lithium ion secondary batteries to form a pseudo-spinel-type crystal structure, the problem of reduced capacity and poor circulation performance of lithium ion secondary batteries during charge and discharge cycles is solved, and higher cycle stability and safety are achieved.
Patent Information
- Application Number
- JP2024108394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-17
- Filing Date
- 2024-07-04
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2039-07-24
AI Technical Summary
The existing lithium-ion secondary batteries have reduced capacity and poor circulation performance during charging and discharge cycles, and the release of transition metals such as cobalt is prone to occur during long-term charging of high voltage, which affects safety and reliability.
The positive electrode active substance containing lithium, cobalt, magnesium, oxygen and fluorine was used to determine its crystal structure as an R-3m space group through powder X-ray diffraction analysis, and magnesium and fluorine were added during the manufacturing process to form a pseudo-spinel-type crystal structure to improve the cycle stability and safety of the battery.
It effectively suppresses the capacity of the positive electrode active substance during charging and discharging, improves the cycling performance and safety of lithium-ion secondary batteries, reduces the release of transition metals, and enhances the high-voltage stability of the battery.
Smart Images

Figure 0007663752000006 
Figure 0007663752000007 
Figure 0007663752000008
Abstract
Description
[Technical field]
[0001] One aspect of the present invention relates to an object, a method, or a manufacturing method. Process, machine, manufacture, or composition of matter One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or the like. In particular, the present invention relates to a secondary battery that can be used in a semiconductor device, an electronic device, or a method for manufacturing the same. The present invention relates to a positive electrode active material, a secondary battery, and an electronic device having the secondary battery.
[0002] In this specification, the term "electricity storage device" refers to any element or device having an electricity storage function. For example, lithium-ion secondary batteries and other storage batteries (also called secondary batteries) These include lithium ion capacitors and electric double layer capacitors.
[0003] In addition, in this specification, the term "electronic device" refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic devices. [Background technology]
[0004] In recent years, various types of energy storage devices, such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries, have become available. The development of lithium-ion batteries, which have high power output and high energy density, is particularly active. Secondary batteries are used in mobile phones, smartphones, tablets, and notebook computers. Mobile information terminals, portable music players, digital cameras, medical equipment, next-generation clean energy Hybrid vehicles (HEVs, electric vehicles (EVs), plug-in hybrids) Demand for rechargeable vehicles (PHEVs, etc.) is expanding rapidly along with the development of the semiconductor industry. As a source of energy, it has become indispensable in today's information society.
[0005] The characteristics required for lithium-ion secondary batteries are a higher energy density. , improved cycle characteristics, safety in various operating environments, and improved long-term reliability.
[0006] Therefore, we developed a positive electrode to improve the cycle characteristics and capacity of lithium-ion secondary batteries. Improvements to the active material have been investigated (Patent Document 1 and Patent Document 2). Research on the crystal structure is also being conducted (Non-Patent Documents 1 to 3).
[0007] X-ray diffraction (XRD) is one of the techniques used to analyze the crystal structure of positive electrode active materials. ICSD (Inorganic Crystal Structurally Organized Synthetic Dispersion) Analysis of XRD data using the Artificial Intelligence Database can be done.
[0008] Patent Document 3 describes the Jahn-Teller effect in nickel-based layered oxides. There are. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2002-216760 A [Patent Document 2] JP 2006-261132 A [Patent Document 3] JP 2017-188466 A [Non-patent literature]
[0010] [Non-Patent Document 1] Toyoki Okumura et al, “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et al, “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16);165114 [Non-Patent Document 3] Zhaohui Chen et al, “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12) A1604-A1609 [Non-Patent Document 4] WE Counts et al, Journal of the American Ceramic Society,(1953) 36[1] 12-17. Fig.01471 [Non-Patent Document 5] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. Summary of the Invention [Problem to be solved by the invention]
[0011] One aspect of the present invention is a method for producing a lithium ion secondary battery having high capacity and excellent charge / discharge cycle characteristics. It is an object of the present invention to provide a positive electrode active material and a manufacturing method thereof. Another object of the present invention is to provide a method for manufacturing a positive electrode active material. By using it in lithium-ion secondary batteries, the decrease in capacity during charge / discharge cycles is suppressed. Another object of the present invention is to provide a positive electrode active material having a high capacity. Another object of the present invention is to provide a secondary battery having excellent charge-discharge characteristics. Another object of the present invention is to provide a secondary battery that can maintain a charged state at a high voltage for a long period of time. The objective of the present invention is to provide a positive electrode active material in which the elution of transition metals such as cobalt is suppressed even when the positive electrode is maintained at a temperature of 100° C. Another embodiment of the present invention provides a secondary battery with high safety or reliability. One of the challenges we face is to
[0012] Another embodiment of the present invention is a novel substance, active material particles, a power storage device, or a manufacturing method thereof. One of our goals is to provide a method for
[0013] The description of these problems does not preclude the existence of other problems. It is not necessary for one embodiment to solve all of these problems. Problems other than these can be extracted from the claims. [Means for solving the problem]
[0014] One aspect of the present invention is a method for manufacturing a lithium-based lithium-ion battery comprising: The Rietveld solution was obtained for the powder X-ray diffraction pattern using CuKα1 radiation. When the crystal structure was analyzed, it was determined that the crystal structure had the space group R-3m and a molecular weight of 2.814×10 - 10 m or larger, 2.817×10 -10 m and the c-axis lattice constant is 14.0 5×10 -10 m or larger, 14.07×10 -10 m, and can be analyzed by X-ray photoelectron spectroscopy. When the cobalt concentration is taken as 1, the relative value of the magnesium concentration is 1.6 or more. It is a positive electrode active material having a dielectric constant of .0 or less.
[0015] Alternatively, one embodiment of the present invention is a semiconductor material comprising lithium, cobalt, magnesium, oxygen, and fluorine. and a positive electrode active material having the above structure, the positive electrode active material being used in a positive electrode and lithium metal being used in a negative electrode. For lithium-ion secondary batteries, until the battery voltage reaches 4.7V in a 25℃ environment The battery was charged at a constant current, then charged at a constant voltage until the current reached 0.01C. Then, the positive electrode was replaced with CuKα When analyzed by powder X-ray diffraction using a single line, 2θ is 19.10° or more and 19.50° or less. and a second diffraction peak having a 2θ of 45.50° or more and 45.60° or less. and a positive electrode active material having the above structure.
[0016] In any of the above configurations, the positive electrode active material is used for the positive electrode, and lithium metal is used for the negative electrode. The lithium-ion secondary battery used had a battery voltage of 4.7 V in a 25°C environment. After charging at a constant current until the current value reaches 0.01C, the positive electrode is charged at a constant voltage until the current value reaches 0.01C. When analyzed by powder X-ray diffraction using uKα1 radiation, 2θ is 19.10° or more and 19.50° or less. The first diffraction peak is located below the 2θ angle and the second diffraction peak is located at 2θ angles of 45.50° to 45.60°. It is preferable that the flexural member has a fold peak.
[0017] In any one of the above configurations, the amount of magnesium measured by X-ray photoelectron spectroscopy is The concentration is preferably 1.6 or more and 6.0 or less, assuming that the concentration of cobalt is 1.
[0018] In any of the above configurations, nickel, aluminum, and phosphorus are contained. is preferred.
[0019] Alternatively, one embodiment of the present invention is a method for producing a lithium-based lithium-based lithium ion battery comprising mixing a lithium source, a fluorine source, and a magnesium source. A first step of preparing a first mixture, the first mixture comprising lithium, cobalt, and oxygen. a second step of mixing the composite oxide with the first mixture to prepare a second mixture; A third step of heating the mixture of the first and second steps to produce a third mixture, and a third step of heating the third mixture and a second step of heating the third mixture and a third step of heating the third mixture. a fourth step of mixing the fluorine source with the fluorine source to form a fourth mixture; and heating the fourth mixture. and a fifth step of preparing a fifth mixture, In the fourth step, the number of aluminum atoms in the aluminum source is determined to be equal to or smaller than that in the third mixture. A method for producing a positive electrode active material in which the number of cobalt atoms is 0.001 to 0.02 times the number of cobalt atoms contained in the positive electrode active material. It is law.
[0020] In the above configuration, the magnesium source in the first step The number of atoms is 0.005 to 0.05 times the number of cobalt atoms in the composite oxide in the second step. It is preferable that the ratio is 0.5 or less. Effect of the Invention
[0021] According to one aspect of the present invention, a lithium ion secondary battery having high capacity and excellent charge / discharge cycle characteristics is provided. The present invention provides a positive electrode active material for a battery and a method for producing the same. It is possible to provide a method for producing an active material. In addition, it is possible to use the active material in a lithium ion secondary battery. Therefore, it is possible to provide a positive electrode active material in which the decrease in capacity during charge / discharge cycles is suppressed. In addition, it is possible to provide a high-capacity secondary battery. In addition, even if the charged state at a high voltage is maintained for a long period of time, the cobalt It is possible to provide a positive electrode active material in which the elution of transition metals such as zinc is suppressed. In addition, the present invention provides a highly reliable secondary battery. Apparatuses, or methods for making same, may be provided. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a diagram illustrating the charge depth and crystal structure of a positive electrode active material. [Diagram 2] FIG. 2 is a diagram illustrating the charge depth and the crystal structure of the positive electrode active material. [Diagram 3] FIG. 3 is an XRD pattern calculated from the crystal structure. [Figure 4] Fig. 4(A) shows the lattice constant calculated from XRD. Fig. 4(B) shows the lattice constant calculated from XRD. Fig. 4(C) shows the lattice constant calculated from XRD. [Diagram 5] Fig. 5(A) shows the lattice constant calculated from XRD. Fig. 5(B) shows the lattice constant calculated from XRD. Fig. 5(C) shows the lattice constant calculated from XRD. [Figure 6] FIG. 6 illustrates an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 7] FIG. 7 illustrates an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 8] FIG. 8 illustrates an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 9]FIG. 9 illustrates an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention. [Figure 10] Fig. 10(A) is a cross-sectional view of an active material layer in which a graphene compound is used as a conductive additive, and Fig. 10(B) is a cross-sectional view of an active material layer in which a graphene compound is used as a conductive additive. [Figure 11] Fig. 11(A) is a diagram for explaining a method for charging a secondary battery. Fig. 11(B) is a diagram for explaining a method for charging a secondary battery. Fig. 11(C) is a diagram for explaining a method for charging a secondary battery. [Figure 12] Fig. 12(A) is a diagram for explaining a method for charging a secondary battery. Fig. 12(B) is a diagram for explaining a method for charging a secondary battery. Fig. 12(C) is a diagram for explaining a method for charging a secondary battery. [Figure 13] Fig. 13(A) is a diagram for explaining a method for charging a secondary battery, and Fig. 13(B) is a diagram for explaining a method for discharging a secondary battery. [Figure 14] Fig. 14(A) is a diagram for explaining a coin-type secondary battery, Fig. 14(B) is a diagram for explaining a coin-type secondary battery, and Fig. 14(C) is a diagram for explaining current and electrons during charging. [Figure 15] Fig. 15(A) is a diagram explaining a cylindrical secondary battery. Fig. 15(B) is a diagram explaining a cylindrical secondary battery. Fig. 15(C) is a diagram explaining a plurality of cylindrical secondary batteries. Fig. 15(D) is a diagram explaining a plurality of cylindrical secondary batteries. [Figure 16] Fig. 16(A) is a diagram for explaining an example of a battery pack, and Fig. 16(B) is a diagram for explaining an example of a battery pack. [Figure 17] Fig. 17(A1) is a diagram for explaining an example of a secondary battery. Fig. 17(A2) is a diagram for explaining an example of a secondary battery. Fig. 17(B1) is a diagram for explaining an example of a secondary battery. Fig. 17(B2) is a diagram for explaining an example of a secondary battery. [Figure 18] Fig. 18(A) is a diagram for explaining an example of a secondary battery, and Fig. 18(B) is a diagram for explaining an example of a secondary battery. [Figure 19] FIG. 19 is a diagram illustrating an example of a secondary battery. [Figure 20] Fig. 20(A) is a diagram for explaining a laminated type secondary battery, Fig. 20(B) is a diagram for explaining a laminated type secondary battery, and Fig. 20(C) is a diagram for explaining a laminated type secondary battery. [Figure 21] Fig. 21(A) is a diagram illustrating a laminated type secondary battery, and Fig. 21(B) is a diagram illustrating a laminated type secondary battery. [Figure 22] FIG. 22 is a diagram showing the external appearance of a secondary battery. [Figure 23] FIG. 23 is a diagram showing the external appearance of a secondary battery. [Figure 24] Fig. 24(A) is a diagram for explaining a method for manufacturing a secondary battery, Fig. 24(B) is a diagram for explaining a method for manufacturing a secondary battery, and Fig. 24(C) is a diagram for explaining a method for manufacturing a secondary battery. [Diagram 25] Fig. 25(A) is a diagram explaining a bendable secondary battery. Fig. 25(B1) is a diagram explaining a bendable secondary battery. Fig. 25(B2) is a diagram explaining a bendable secondary battery. Fig. 25(C) is a diagram explaining a bendable secondary battery. Fig. 25(D) is a diagram explaining a bendable secondary battery. [Figure 26] Fig. 26(A) is a diagram illustrating a bendable secondary battery, and Fig. 26(B) is a diagram illustrating a bendable secondary battery. [Figure 27] FIG. 27(A) is a diagram for explaining an example of an electronic device. FIG. 27(B) is a diagram for explaining an example of an electronic device. FIG. 27(C) is a diagram for explaining an example of an electronic device. FIG. 27(D) is a diagram for explaining an example of an electronic device. FIG. 27(E) is a diagram for explaining an example of an electronic device. FIG. 27(F) is a diagram for explaining an example of an electronic device. FIG. 27(G) is a diagram for explaining an example of an electronic device. FIG. 27(H) is a diagram for explaining an example of an electronic device. [Figure 28] Fig. 28(A) is a diagram illustrating an example of an electronic device, Fig. 28(B) is a diagram illustrating an example of an electronic device, and Fig. 28(C) is a diagram illustrating an example of an electronic device. [Figure 29] FIG. 29 is a diagram illustrating an example of an electronic device. [Diagram 30] Fig. 30(A) is a diagram illustrating an example of a vehicle, Fig. 30(B) is a diagram illustrating an example of a vehicle, and Fig. 30(C) is a diagram illustrating an example of a vehicle. [Diagram 31] 31A and 31B show the continuous charge tolerance of the secondary battery. [Diagram 32] 32A and 32B show the continuous charging tolerance of the secondary battery. [Diagram 33] 33A and 33B show the cycle characteristics of the secondary battery. [Diagram 34] Fig. 34(A) shows the results of XRD evaluation of the positive electrode, and Fig. 34(B) shows the results of XRD evaluation of the positive electrode. [Diagram 35] Fig. 35(A) shows the results of XRD evaluation of the positive electrode, and Fig. 35(B) shows the results of XRD evaluation of the positive electrode. [Diagram 36] 36(A) and 36(B) show the continuous charging tolerance of the secondary battery. [Figure 37] FIG. 37 shows the cycle characteristics of the secondary battery. [Figure 38] Fig. 38(A) shows a charge / discharge curve of a secondary battery, Fig. 38(B) shows a charge / discharge curve of a secondary battery, and Fig. 38(C) shows a charge / discharge curve of a secondary battery. [Figure 39] Fig. 39(A) shows the results of TEM observation of the positive electrode active material, and Fig. 39(B) shows the results of EDX analysis of the positive electrode active material. [Diagram 40] Fig. 40(A) shows the results of XRD evaluation of the positive electrode, and Fig. 40(B) shows the results of XRD evaluation of the positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the following description, and it is understood by those skilled in the art that various changes can be made in form and detail. The present invention is not limited to the description of the following embodiments. It is not something that is done.
[0024] In this specification and the like, crystal planes and directions are indicated by Miller indices. In crystallography, numbers are usually marked with a superscript bar. Instead of putting a bar above the letter, numbers are sometimes expressed by putting a - (minus sign) before them. In addition, individual orientations that indicate directions within a crystal are indicated by [ ], and a collective orientation that indicates all equivalent directions is indicated by The symbols are < >, individual crystal faces are ( ), and collective faces with equivalent symmetry are {}. Each one is expressed.
[0025] In this specification, segregation refers to a phenomenon in which a solid consisting of multiple elements (e.g., A, B, C) This refers to the phenomenon in which a certain element (e.g. B) is distributed spatially non-uniformly.
[0026] In this specification, the surface layer of a particle of an active material or the like refers to a region from the surface to about 10 nm. The surface caused by cracks or fissures can also be called the surface. , called inside.
[0027] In the present specification and the like, a layered rock-salt type crystal of a composite oxide containing lithium and a transition metal The structure is a rock-salt type ion arrangement in which cations and anions are arranged alternately, and is Since lithium is regularly arranged to form a two-dimensional plane, two-dimensional diffusion of lithium is possible. The term "crystal structure" refers to a crystal structure in which the crystal structure has defects such as a deficiency of cations or anions. Strictly speaking, the layered rock salt crystal structure is a case where the lattice of the rock salt crystal is distorted. There is.
[0028] In the present specification and the like, a rock salt type crystal structure refers to a structure in which cations and anions are arranged alternately. The structure may contain a cation or anion defect.
[0029] In the present specification and the like, the pseudospinel type of a composite oxide containing lithium and a transition metal The crystal structure of is in the space group R-3m, and is not a spinel type crystal structure, but it is a cobalt The cation arrangement is similar to that of the spinel type, with ions such as magnesium occupying the 6-coordinate oxygen sites. It is a crystalline structure that has symmetry. The pseudo-spinel type crystal structure is characterized by the absence of light elements such as lithium. The atoms may occupy the 4-coordinate oxygen sites, and in this case the ionic arrangement is similar to that of the spinel type. It has symmetry.
[0030] The pseudospinel crystal structure has random Li between layers, but the CdCl2 type It can be said that the crystal structure is similar to that of the CdCl2 type. The crystal structure is shown in Fig. 1 when lithium nickel oxide is charged to a charge depth of 0.94 (Li 0.06 Ni O2), but pure lithium cobalt oxide or layered cobalt-rich It is known that rock-salt type positive electrode active materials do not usually have this crystal structure.
[0031] Layered rock salt crystals and the anions of rock salt crystals are in a cubic close-packed structure (face-centered cubic lattice structure) ) It is assumed that the anions in pseudospinel crystals also form a cubic close-packed structure. When these contact, a crystal plane exists where the cubic close-packed structure formed by the anions is oriented in the same direction. However, the space group of layered rock salt crystals and pseudospinel crystals is R-3m, and that of rock salt The space groups of the Fm-3m type crystals (the common rock salt type crystal space group) and Fd-3m (the simplest Since the space group is different from that of rock salt crystals, which have a perfect symmetry, the crystal planes that satisfy the above conditions must be aligned. The Raman index is different between layered rock salt crystals and pseudospinel crystals and between rock salt crystals. In the layered rock salt crystal, pseudospinel crystal, and rock salt crystal, the anions When the orientation of the cubic close-packed structure is aligned, the crystal orientation is roughly the same. There is.
[0032] The crystal orientation of the two regions roughly coincides with each other, as can be seen from TEM (transmission electron microscope) images and STE M (scanning transmission electron microscope) image, HAADF-STEM (high angle annular dark field scanning transmission electron microscope) image This should be judged from images obtained using a bright-field scanning electron microscope (ABF-STEM), etc. X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can also be used as a basis for judgment. In a TEM image, the arrangement of cations and anions is observed as repeated bright and dark lines. When the orientation of the cubic close-packed structure in the layered rock salt crystal and the rock salt crystal is aligned, the crystal Between the two, the angle between the repeated bright and dark lines is 5 degrees or less, and more preferably 2.5 degrees or less. In addition, light elements such as oxygen and fluorine are clearly visible in TEM images. In some cases, it may not be possible to determine the alignment of the metal elements. do.
[0033] In this specification, the theoretical capacity of the positive electrode active material refers to the amount of intercalation and deintercalation that the positive electrode active material has. The theoretical capacity of LiCoO2 is 27 4mAh / g, the theoretical capacity of LiNiO2 is 274mAh / g, the theoretical capacity of LiMn2O4 is is 148mAh / g.
[0034] In the present specification, the depth of charge when all intercalable and detachable lithium is intercalated is The charge depth when all the intercalable lithium in the positive electrode active material is deintercalated is 1. Let's assume that this is the case.
[0035] In this specification, charging refers to transferring lithium ions from the positive electrode to the negative electrode in the battery. The positive electrode active material transfers electrons from the negative electrode to the positive electrode in an external circuit. In this case, charging refers to the process of releasing lithium ions. Also, when the charge depth is 0.7 or more, Positive electrode active materials with a charge voltage of .9 or less are sometimes referred to as positive electrode active materials charged at high voltage.
[0036] Similarly, discharging means moving lithium ions from the negative electrode to the positive electrode within the battery and discharging them from the external circuit. The term refers to the transfer of electrons from the positive electrode to the negative electrode in a path. The insertion of ions is called discharging. The positive electrode active material was discharged from a high-voltage charged state to 90% or more of its charge capacity. This refers to the positive electrode active material discharged in minutes.
[0037] In this specification, a non-equilibrium phase change refers to a phenomenon that causes a non-linear change in a physical quantity. For example, the capacitance (Q) is differentiated by the voltage (V) to obtain A non-equilibrium phase change occurs before and after the peak in the dQ / dV curve, and the crystal structure changes significantly. It is believed that this is the case.
[0038] (Embodiment 1) In this embodiment, a positive electrode active material of one embodiment of the present invention will be described.
[0039] [Positive electrode active material structure] Materials with a layered rock-salt crystal structure, such as lithium cobalt oxide (LiCoO2), are It is known that it has a high capacitance and is an excellent positive electrode active material for secondary batteries. An example of a material having a crystal structure is a composite oxide represented by LiMO2. An example of M is one or more selected from Co and Ni. In addition to one or more selected from Co and Ni, one or more selected from Al and Mn are Some examples include:
[0040] The Jahn-Teller effect in transition metal compounds depends on the number of electrons in the d orbitals of the transition metal: The strength of the effect is known to vary.
[0041] In nickel-containing compounds, distortion may occur due to the Jahn-Teller effect. Therefore, when LiNiO2 is charged and discharged at high voltage, the distortion In LiCoO2, the Jahn-Teller effect is This suggests that the effect of the charge / discharge resistance at high voltages is small, and this is preferable because the resistance may be better. It is.
[0042] The positive electrode active material will be described with reference to Figs. 1 and 2. The case where cobalt is used as the transition metal in the substance will be described.
[0043] <Cathode active material 1> The positive electrode active material 100C shown in FIG. 2 is prepared by the method described below. The lithium cobalt oxide (LiCoO2) shown in Figure 2 is a lithium cobalt oxide with no added lithium. As described in Non-Patent Documents 1 and 2, etc., the charge depth of the lithium-ion battery varies depending on The crystal structure changes.
[0044] As shown in Figure 1, lithium cobalt oxide at a charge depth of 0 (discharged state) is in the space group R- It has a region with a 3m crystal structure, and there are three CoO2 layers in the unit cell. Therefore, this crystal structure is sometimes called the O3 type crystal structure. The term refers to a structure in which an octahedral structure in which oxygen is six-coordinated is connected to a plane in an edge-sharing state. .
[0045] At a charge depth of 1, the crystal structure has the space group P-3m1, and the unit cell contains Co There is one O2 layer, so this crystal structure is sometimes called the O1 type crystal structure.
[0046] In addition, when the charge depth is about 0.88, lithium cobalt oxide has a crystal structure in the space group R-3m. This structure is similar to the P-3m1(O1) structure of CoO2 and the R-3m(O 3) The LiCoO2 structure and the structure of the LiCoO2 layered alternately. The crystal structure is sometimes called the H1-3 type crystal structure. However, in reality, the H1-3 type crystal structure has twice as many cobalt atoms per unit cell as the other structures. However, In this specification, the c-axis of the H1-3 crystal structure is used as a unit to facilitate comparison with other structures. This will be shown in a diagram showing half of a knit cell.
[0047] As an example of the H1-3 type crystal structure, as described in Non-Patent Document 3, the unit cell is The coordinates of cobalt and oxygen in are Co(0, 0, 0.42150±0.00016), O 1(0, 0, 0.27671±0.00045), O2(0, 0, 0.11535±0. 00045), where O1 and O2 are oxygen atoms. The H1-3 crystal structure is a unit cell with one cobalt and two oxygen atoms. On the other hand, as described later, the pseudospinel type crystal structure of one embodiment of the present invention is preferably is represented by a unit cell with one cobalt and one oxygen. The symmetry of cobalt and oxygen is different between the spinel structure and the H1-3 structure. The pseudospinel structure is less different from the O3 structure than the H1-3 structure. It is preferable to use any one of the unit cells to represent the crystal structure of the positive electrode active material. For example, the selection of GOF (good of field) in the Rietveld analysis of XRD is fitness) should be selected to be smaller.
[0048] High-voltage charging with a charging voltage of 4.6 V or higher based on the redox potential of lithium metal When the battery is repeatedly charged or discharged to a deep depth of charge of 0.8 or more, Lithium cobalt oxide has a H1-3 type crystal structure and a R-3m(O3) structure in the discharged state. The crystal structure changes (i.e., non-equilibrium phase changes) between these two states.
[0049] However, these two crystal structures have a large misalignment of the CoO2 layers. As shown by the arrows and the lines in the figure, in the H1-3 crystal structure, the CoO2 layer is separated from the R-3m(O3) by a large Such dynamic structural changes adversely affect the stability of the crystal structure. Yes.
[0050] Furthermore, the difference in volume is also large. When comparing per the same number of cobalt atoms, the H1-3 type crystal The volume difference between the O3-type crystal structure and the discharged O3-type crystal structure is more than 3.0%.
[0051] In addition, the H1-3 type crystal structure has continuous CoO2 layers such as P-3m1(O1). Such a structure is likely to be unstable.
[0052] Therefore, repeated high-voltage charging and discharging causes the crystal structure of lithium cobalt oxide to break down. The breakdown of the crystal structure causes the deterioration of cycle characteristics. This reduces the number of sites where lithium can exist stably, and makes it difficult to insert and remove lithium. This is thought to be the reason.
[0053] <Cathode active material 2> ≪Inside≫ In the positive electrode active material according to one embodiment of the present invention, the CoO2 layer is displaced during repeated high-voltage charging and discharging. Furthermore, the change in volume can be reduced. The positive electrode active material according to one embodiment of the present invention can achieve excellent cycle characteristics. The positive electrode active material according to one embodiment of the present invention can have a stable crystal structure in a high-voltage charged state. In other words, the positive electrode active material of one embodiment of the present invention has a short circuit when a high-voltage charged state is maintained. In such cases, safety is improved, making it preferable. .
[0054] In the positive electrode active material according to one embodiment of the present invention, the positive electrode active material has a sufficiently discharged state and a high-voltage charged state. The change in crystal structure and the difference in volume when compared per the same number of transition metal atoms in small.
[0055] The crystal structure of the positive electrode active material 100A before and after charging and discharging is shown in FIG. It is a composite oxide containing titanium, cobalt, and oxygen. In addition to the above, it also contains magnesium. It is also preferable that the group contains a halogen atom such as fluorine or chlorine.
[0056] The crystal structure at charge depth 0 (discharged state) in Figure 2 is the same as that in Figure 1, R-3m(O3). On the other hand, when the positive electrode active material 100A is fully charged, it has a different crystal structure from the H1-3 type. It has a crystal with a different structure. This structure is in the space group R-3m, and the spinel type crystal structure is However, ions such as cobalt and magnesium occupy the 6-coordinate oxygen sites, and the coordination of cations The rows have a symmetry similar to that of the spinel type. Therefore, this structure is referred to as a pseudospinel type in this specification. In the crystal structure of the pseudospinel type shown in Figure 2, cobalt In order to explain the symmetry of the atom and the symmetry of the oxygen atom, the lithium symbol is omitted. However, in reality, lithium exists between the CoO2 layers at a ratio of, for example, 20 atomic % or less relative to cobalt. In addition, in both the O3 type and pseudospinel type crystal structures, CoO2 It is preferable that magnesium is present in a dilute state between the layers, i.e., at the lithium site. It is preferable that halogen such as fluorine is present randomly and dilutely at the oxygen sites.
[0057] In addition, in the pseudospinel crystal structure, light elements such as lithium occupy the oxygen tetracoordination site. In some cases, the arrangement of ions has a symmetry similar to that of the spinel type.
[0058] The pseudospinel crystal structure has random Li between layers, but the CdCl2 type It can be said that the crystal structure is similar to that of the CdCl2 type. The crystal structure is shown in Fig. 1 when lithium nickel oxide is charged to a charge depth of 0.94 (Li0.06 Ni O2), but pure lithium cobalt oxide or layered cobalt-rich It is known that rock-salt type positive electrode active materials do not usually have this crystal structure.
[0059] Layered rock salt crystals and the anions of rock salt crystals are in a cubic close-packed structure (face-centered cubic lattice structure) ) It is assumed that the anions in pseudospinel crystals also form a cubic close-packed structure. When these contact, a crystal plane exists where the cubic close-packed structure formed by the anions is oriented in the same direction. However, the space group of layered rock salt crystals and pseudospinel crystals is R-3m, and that of rock salt The space groups of the Fm-3m type crystals (the common rock salt type crystal space group) and Fd-3m (the simplest Since the space group is different from that of rock salt crystals, which have a perfect symmetry, the crystal planes that satisfy the above conditions must be aligned. The Raman index is different between layered rock salt crystals and pseudospinel crystals and between rock salt crystals. In the layered rock salt crystal, pseudospinel crystal, and rock salt crystal, the anions When the orientation of the cubic close-packed structure is aligned, the crystal orientation is roughly the same. There is.
[0060] In the positive electrode active material 100A, when a large amount of lithium is released by charging at a high voltage, the crystal structure The change in the positive electrode active material 100C is suppressed more than that in the positive electrode active material 100C. For example, as shown by the dotted line in FIG. Additionally, there is almost no misalignment of the CoO2 layers in these crystal structures.
[0061] More specifically, the positive electrode active material 100A has a stable structure even when the charging voltage is high. For example, the charge voltage at which the positive electrode active material 100C becomes an H1-3 type crystal structure, e.g. For example, even at a voltage of about 4.6 V based on the potential of lithium metal, the positive electrode active material 100 In A, there is a region of charging voltage where the crystal structure of R-3m(O3) can be maintained. For example, the potential of lithium metal is about 4.65V to 4.7V. There is also a region where the pseudo-spinel crystal structure can be formed even at high charging voltages. In some cases, H1-3 type crystals can be observed only after the battery is cooled. For example, when graphite is used as the negative electrode active material, the voltage of the secondary battery is 4.3V or more and 4.5V or more. V or less, there exists a region of charging voltage where the crystal structure of R-3m(O3) can be maintained. The charging voltage is further increased, for example, to 4.35V or higher based on the potential of lithium metal. Even below 55V, there exists a region in which the pseudospinel crystal structure can be formed.
[0062] Therefore, in the positive electrode active material 100A, the crystal structure remains unchanged even after repeated charging and discharging at high voltages. It doesn't crumble easily.
[0063] In the pseudospinel crystal structure, the coordinates of cobalt and oxygen in the unit cell are (0,0,0.5), O(0,0,x), 0.20≦x≦0.25 can.
[0064] Magnesium exists randomly and dilutely between the CoO2 layers, i.e., on the lithium sites. This has the effect of suppressing the displacement of the CoO2 layers. Therefore, magnesium is a positive electrode active material with a 100% It is preferable that A is distributed throughout the particles. It is also preferable to distribute magnesium throughout the particles. For this reason, it is preferable to carry out a heat treatment in the process of producing the positive electrode active material 100A.
[0065] However, if the heat treatment temperature is too high, cation mixing occurs and magnesium The presence of magnesium in the cobalt site increases the possibility of magnesium entering the cobalt site. If the heat treatment temperature is too high, the effect of maintaining the R-3m structure will be lost. However, there are concerns that the negative effects of reducing cobalt to divalent form and evaporating lithium may occur. can be.
[0066] Therefore, before the heat treatment to distribute magnesium throughout the particles, cobalt oxide was added. It is preferable to add a halogen compound such as a fluorine compound to lithium. Adding substances to lithium cobalt oxide lowers its melting point. At a temperature where on-mixing is unlikely to occur, it is easy to distribute magnesium throughout the particles. Furthermore, if fluorine compounds are present, the electrolyte decomposes and produces hydrofluoric acid, which increases corrosion resistance. can be expected to improve.
[0067] If the magnesium concentration is increased beyond a desired value, the effect of stabilizing the crystal structure is reduced. Magnesium may be present at the cobalt site in addition to the lithium site. This is believed to be because the magnesium oxide contained in the positive electrode active material according to one embodiment of the present invention is also included in the The number of um atoms is preferably 0.001 times or more and 0.1 times or less the number of cobalt atoms, and more preferably 0.0 More preferably, the ratio is greater than 1 and less than 0.04, and even more preferably, about 0.02. The magnesium concentration shown in is determined by, for example, measuring the magnesium content of the entire positive electrode active material particle using ICP-MS or the like. It may be a value obtained by elementary analysis, or a value based on the composition of raw materials in the process of producing the positive electrode active material. It may be based on.
[0068] Lithium cobalt oxide is added with metals other than cobalt (hereinafter referred to as metal Z), such as nickel, One or more metals selected from aluminum, manganese, titanium, vanadium and chromium They may be added, and it is particularly preferable to add at least one of nickel and aluminum. Manganese, titanium, vanadium and chromium may be stable and tend to have 4 valences. The addition of metal Z may contribute to the stability of the positive electrode of one embodiment of the present invention. For example, in some materials, the crystal structure becomes more stable when the material is charged at a high voltage. In the positive electrode active material according to one embodiment of the present invention, the metal Z improves the crystallinity of the lithium cobalt oxide. It is preferable to add it at a concentration that does not significantly change the amount of the additive. It is preferable that the amount is such that no effect is exhibited.
[0069] As the magnesium concentration of the positive electrode active material of one embodiment of the present invention increases, the capacity of the positive electrode active material increases. The amount of lithium in the alloy may decrease. For example, magnesium may enter the lithium site. This may reduce the amount of lithium that contributes to charging and discharging. In some cases, magnesium may produce magnesium compounds that do not contribute to charging and discharging. The positive electrode active material according to one embodiment of the present invention contains nickel as the metal Z in addition to magnesium. In some cases, the capacity per weight and volume can be increased. In one embodiment of the positive electrode active material, in addition to magnesium, aluminum is contained as the metal Z. In some cases, the capacity per weight and per volume can be increased. The positive electrode active material of one embodiment of the present invention contains nickel and aluminum in addition to magnesium. This may allow for higher capacity per weight and volume.
[0070] The concentrations of elements such as magnesium and metal Z contained in the positive electrode active material of one embodiment of the present invention are described below. is expressed using the number of atoms.
[0071] The number of nickel atoms in the positive electrode active material of one embodiment of the present invention is 7.5 times the number of cobalt atoms. % or less, more preferably 0.05% to 4%, and even more preferably 0.1% to 2%. The nickel concentration shown here is more preferably determined by, for example, ICP-MS or the like using a positive electrode active material. The value may be obtained by performing elemental analysis on the entire particle, or may be obtained by performing elemental analysis on the raw material in the process of producing the positive electrode active material. The value of the blend may be based on the amount of the ingredients.
[0072] The number of aluminum atoms in the positive electrode active material of one embodiment of the present invention is 0.1 times the number of cobalt atoms. The range is preferably 0.05% or more and 4% or less, and more preferably 0.1% or more and 2% or less. The aluminum concentration can be determined by, for example, elemental analysis of the entire particles of the positive electrode active material using ICP-MS. The value may be based on the composition of the raw materials in the process of producing the positive electrode active material. Good too.
[0073] The positive electrode active material of one embodiment of the present invention preferably contains an element X, and the element X is preferably phosphorus. In addition, the positive electrode active material of one embodiment of the present invention is preferably a compound containing phosphorus and oxygen. It is more preferable that the .alpha.-methylphenyl.
[0074] The positive electrode active material according to one embodiment of the present invention contains a compound containing element X, and thus the positive electrode active material can be used for high-voltage charging. When the above state is maintained, a short circuit may be less likely to occur.
[0075] In the case where the positive electrode active material according to an embodiment of the present invention contains phosphorus as the element X, the electrolyte decomposes. This may cause the hydrogen fluoride generated to react with phosphorus, resulting in a decrease in the hydrogen fluoride concentration in the electrolyte. do.
[0076] If the electrolyte contains LiPF6, hydrogen fluoride may be generated due to hydrolysis. In addition, hydrogen fluoride is produced by the reaction of PVDF, which is used as a component of the positive electrode, with alkali. The decrease in hydrogen fluoride concentration in the electrolyte may cause corrosion of the current collector. In addition, it may be possible to prevent the loss of adhesion caused by gelation or insolubilization of PVDF. It may be possible to suppress the decline.
[0077] When the positive electrode active material according to one embodiment of the present invention contains magnesium in addition to the element X, high voltage charging When element X is phosphorus, the number of phosphorus atoms is 1 / 1000 that of cobalt. The number of atoms of 1% or more and 20% or less is preferably 2% or more and 10% or less, more preferably 3% or more. More preferably, the number of magnesium atoms is 0.1 times the number of cobalt atoms. 0.1% or more and 10% or less is preferable, 0.5% or more and 5% or less is more preferable, 0.7% or more More preferably, the phosphorus and magnesium concentrations are 4% or less. The value may be obtained by performing elemental analysis of the entire particles of the positive electrode active material using MS or the like. It may be based on the value of the raw material blend in the quality production process.
[0078] When the positive electrode active material has cracks, phosphorus, more specifically, for example, phosphorus and acid, is present inside the cracks. The presence of a compound containing an element may inhibit the progression of cracks.
[0079] ≪Surface layer≫ It is preferable that magnesium is distributed throughout the particles of the positive electrode active material 100A. In addition, it is preferable that the magnesium concentration in the surface layer of the particle is higher than the average concentration in the whole particle. For example, the magnesium concentration in the particle surface layer measured by XPS etc. is different from that measured by ICP-MS etc. It is preferable that the magnesium concentration is higher than the average magnesium concentration of the whole grain to be treated.
[0080] In addition, the positive electrode active material 100A may contain elements other than cobalt, such as nickel, aluminum, ma, etc. In the case where the composition contains one or more metals selected from the group consisting of calcium, iron and chromium, particles of the metal It is preferable that the concentration in the surface layer is higher than the average concentration in the whole particle. The concentration of elements other than cobalt in the surface layer of the particles to be measured is measured by ICP-MS, etc. It is preferable that the concentration is higher than the overall average concentration of the element.
[0081] The particle surface is, so to speak, entirely made up of crystal defects, and lithium is removed from the surface during charging. As the lithium concentration in the upper part of the battery increases, it becomes unstable. If the magnesium concentration in the surface layer is high, the crystal structure will be easily broken. This makes it possible to more effectively suppress structural changes. In addition, the magnesium concentration in the surface layer is high. It is also expected that the corrosion resistance against hydrofluoric acid produced by decomposition of the electrolyte will be improved.
[0082] In addition, the concentration of halogens such as fluorine in the surface layer of the positive electrode active material 100A is higher than the average concentration of the whole particle. The presence of halogen in the surface layer, which is the region in contact with the electrolyte, Therefore, the corrosion resistance against hydrofluoric acid can be effectively improved.
[0083] In this way, the surface layer of the positive electrode active material 100A has a higher concentration of magnesium and fluorine than the inside. It is preferable that the composition of the inner part is different from that of the inner part, and that the composition of the inner part is stable at room temperature. Therefore, even if the surface layer has a different crystal structure from the inside, For example, at least a part of the surface layer of the positive electrode active material 100A has a rock salt type crystal structure. In addition, when the surface layer and the inside have different crystal structures, It is preferable that the orientations of the two are approximately the same.
[0084] However, if the surface layer is made up of only MgO or a solid solution of MgO and CoO(II), Therefore, the surface layer must contain at least cobalt. In the discharged state, the material must also have lithium and must have a path for lithium insertion and removal. It is also preferred that the concentration of cobalt is higher than that of magnesium.
[0085] In addition, the element X is preferably located near the surface of the particles of the positive electrode active material 100A. For example, the positive electrode active material 100A may be covered with a coating containing the element X.
[0086] ≪Grain boundary≫ The magnesium or halogen contained in the positive electrode active material 100A is randomly and dilutely distributed inside. Although they may be present, it is more preferable that a portion of them is segregated at the grain boundaries.
[0087] In other words, the magnesium concentration at and near the grain boundaries of the positive electrode active material 100A is also It is preferable that the halogen concentration at the grain boundary and its vicinity is higher than that at other regions. Preferably higher than other areas of the interior.
[0088] Like the particle surface, the grain boundaries are also planar defects. Therefore, they are prone to instability and changes in the crystal structure. Therefore, if the magnesium concentration at and near the grain boundaries is high, This makes it possible to more effectively suppress changes in the crystal structure.
[0089] In addition, when the magnesium and halogen concentrations at and near the grain boundaries are high, the positive electrode activity Even if a crack occurs along the grain boundary of a grain of material 100A, The magnesium and halogen concentrations are high near the surface. This is why cracks occur. The corrosion resistance of the subsequent positive electrode active material to hydrofluoric acid can also be improved.
[0090] In this specification, the vicinity of the grain boundary refers to the region within about 10 nm from the grain boundary. We have decided to do so.
[0091] ≪Particle size≫ If the particle size of the positive electrode active material 100A is too large, it becomes difficult for lithium to diffuse. On the other hand, if the distance is too small, the surface of the active material layer becomes too rough when the active material layer is applied. Problems such as difficulty in supporting the active material layer when coating the current collector and excessive reaction with the electrolyte Therefore, the average particle size (D50: also called the median size) is 1 μm or more. Preferably, the thickness is 100 μm or less, more preferably, 2 μm to 40 μm, and more preferably, 5 μm More preferably, the thickness is not less than 30 μm.
[0092] <Analysis method> According to one aspect of the present invention, a positive electrode active material exhibits a pseudospinel type crystal structure when charged at a high voltage. Whether or not the positive electrode active material 100A is of the embodiment can be determined by measuring the positive electrode charged at a high voltage using XRD, electron beam Analysis using diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD can be used to determine the symmetry of transition metals such as cobalt contained in the positive electrode active material. The properties of the crystals can be analyzed with high resolution, the degree of crystallinity and the orientation of the crystals can be compared, and the lattice period can be The positive electrode obtained by disassembling a secondary battery can be measured as is, allowing the analysis of the thermal distortion and crystallite size. This is preferable in that sufficient accuracy can be obtained even if the measurement is performed with a small amount of measurement.
[0093] As described above, the positive electrode active material 100A according to one embodiment of the present invention is in a state where it is charged at a high voltage. The characteristic of this battery is that the crystal structure changes little when it is charged and discharged. Materials with a crystal structure that exhibits large changes in the charge and discharge states and that accounts for 50 wt% or more of the material are resistant to high-voltage charging and discharging. Moreover, the desired crystal structure cannot be obtained by merely adding impurity elements. It should be noted that there are cases where the magnesium and fluorine-containing Although they have in common the fact that they are lithium valence oxides, they are pseudo-spinel-type when charged at high voltages. The crystal structure is 60wt% or more, and the H1-3 type crystal structure is 50wt% or more. In some cases, the pseudo-spinel crystal structure is almost 100 wt% at a certain voltage. If the voltage is increased further, the H1-3 crystal structure may be generated. Therefore, in order to determine whether the positive electrode active material 100A is one embodiment of the present invention, it is necessary to measure the amount of the positive electrode active material by XRD or the like. Analysis of the crystal structure is needed.
[0094] However, the crystal structure of the positive electrode active material in a high-voltage charged or discharged state changes when it comes into contact with the air. For example, the crystal structure may change from a pseudo-spinel type to an H1-3 type. Therefore, all samples were heated in an inert atmosphere such as argon. It is preferable to use a bonding method.
[0095] ≪Charging method≫ In order to determine whether a certain composite oxide is the positive electrode active material 100A of one embodiment of the present invention, For example, high-voltage charging of a coin cell (CR2032 type, diameter 20 mm) with lithium as the counter electrode is It is possible to create a battery with a height of 3.2 mm and charge it.
[0096] More specifically, the positive electrode is formed by mixing a positive electrode active material, a conductive additive, and a binder in a slurry. The above-mentioned composition may be applied to an aluminum foil positive electrode current collector for use.
[0097] Lithium metal can be used for the counter electrode. Note that if a material other than lithium metal is used for the counter electrode, When the secondary battery is in a charged state, the potential of the secondary battery is different from the potential of the positive electrode. is the potential of the positive electrode unless otherwise specified.
[0098] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte used was ethylene carbonate (EC) and diethyl carbonate (DEC). EC:DEC=3:7 (volume ratio), vinylene carbonate (VC) was mixed at 2 wt%. The above can be used.
[0099] The separator can be made of polypropylene having a thickness of 25 μm.
[0100] The positive and negative electrode cans can be made of stainless steel (SUS). Cut.
[0101] The coin cell prepared under the above conditions was charged at a constant current of 4.6 V and 0.5 C, and then the current value Charge at a constant voltage until the temperature becomes 0.01C. Here, 1C is 137mA / g. After charging in this way, place the coin cell in a glow plug in an argon atmosphere. By disassembling it in the box and removing the positive electrode, the positive electrode active material charged at high voltage is obtained. When various analyses are carried out after this, the container is sealed in an argon atmosphere to prevent reactions with external components. For example, XRD can be performed in a sealed container with an argon atmosphere. can.
[0102] <XRD> The CuKα1 calculated from the pseudospinel crystal structure and the H1-3 crystal structure model The ideal powder XRD pattern by the line is shown in Figure 3. For comparison, the LiC The ideal X calculated from the crystal structure of oO2(O3) and CoO2(O1) at charge depth 1 The RD patterns are also shown. The patterns of LiCoO2(O3) and CoO2(O1) are ICSD(Inorganic Crystal Structure Database) e) (see Non-Patent Document 5) Materials Stud Reflex Powder Dif, one of the modules of io(BIOVIA) The 2θ range was from 15° to 75°, and the step s ize=0.01, wavelength λ1=1.540562×10 -10 m, λ2 is not set, Mo The nochromator was single. The H1-3 crystal structure pattern is non-patented. It was similarly created from the crystal structure information described in Reference 3. The pseudospinel crystal structure pattern is The crystal structure of the positive electrode active material according to one embodiment of the present invention was estimated from the XRD pattern and analyzed using TOPAS ve The fitting was performed using r.3 (crystal structure analysis software manufactured by Bruker) and was compared with other Similarly, XRD patterns were generated.
[0103] As shown in Figure 3, in the pseudospinel crystal structure, 2θ = 19.30 ± 0.20° (1 9.10° to 19.50°), and 2θ=45.55±0.10° (45.45 Diffraction peaks appear at 2θ = 19. 30±0.10° (19.20° to 19.40°) and 2θ=45.55±0 A sharp diffraction peak appears at .05° (45.50° to 45.60°). However, H1 No peaks appear at these positions in the -3 crystal structure and CoO2 (P-3m1, O1). Therefore, when charged at high voltage, 2θ = 19.30 ± 0.20°, and 2θ The appearance of a peak at 45.55±0.10° indicates that the positive electrode active material 10 according to one embodiment of the present invention This can be said to be a characteristic of 0A.
[0104] This is the crystal structure at 0 charge depth and the crystal structure at high voltage charging, and the diffraction peaks of XRD are More specifically, the main diffraction peaks of both are close to each other. The difference in the positions at which the peaks appear is 2θ = 0.7 or less, and more preferably, 2θ = 0.5 or less.
[0105] It should be noted that the positive electrode active material 100A according to one embodiment of the present invention forms a pseudo-spinel crystal when charged at a high voltage. However, not all of the particles need to have a pseudo-spinel type crystal structure. It may contain a crystalline structure or may be partially amorphous. However, regarding the XRD pattern, When Rietveld analysis was performed on the sample, the pseudo-spinel crystal structure was found to be 50 wt% or more. It is preferably 60 wt% or more, more preferably 66 wt% or more. It is more preferable that the pseudo-spinel type crystal structure is 50 wt% or more, more preferably 60 wt% or more. Furthermore, if the content is more preferably 66 wt % or more, the positive electrode active material has sufficiently excellent cycle characteristics. It is possible.
[0106] In addition, even after more than 100 charge / discharge cycles from the start of the measurements, Rietveld analysis was performed. In this case, the pseudo-spinel crystal structure is preferably 35 wt% or more, and more preferably 40 wt% or more. It is more preferable that the content is 43 wt % or more, and further preferably 43 wt % or more.
[0107] In addition, the crystallite size of the pseudospinel crystal structure of the positive electrode active material particles changes in the discharged state. The charge / discharge current of the positive electrode is only about 1 / 10 of that of LiCoO2(O3). Even under the same XRD measurement conditions, the peaks of the clear pseudospinel crystal structure were not observed after high-voltage charging. On the other hand, in the simple LiCoO2, some of the crystal structures resemble pseudospinel type. Even if a structure can be obtained, the crystallite size will be small and the peaks will be broad and small. The crystallite size can be determined from the half-width of the XRD peak.
[0108] As described above, in the positive electrode active material according to one embodiment of the present invention, the influence of the Jahn-Teller effect is small. The positive electrode active material according to one embodiment of the present invention has a layered rock salt type crystal structure and has a transition It is preferable that the transition metal is mainly cobalt. In materials where the influence of the Jahn-Teller effect is small, other than cobalt, It may have the metal Z mentioned.
[0109] In the positive electrode active material, XRD analysis was used to predict that the influence of the Jahn-Teller effect was small. We consider the range of lattice parameters that can be used.
[0110] 4(A) and (B) show that the positive electrode active material according to one embodiment of the present invention has a layered rock salt type crystal structure. In the case of cobalt and nickel, the lattice definitions of the a-axis and c-axis were determined using XRD. The results of estimating the number of nuclei are shown in Fig. 4(A) for the a-axis and Fig. 4(B) for the c-axis. The XRD used to calculate the lattice constants shown in Figures 4(A) and (B) was obtained by synthesizing the positive electrode active material. The powder is after it has been mixed with nickel and before it is incorporated into the positive electrode. The nickel concentration is calculated based on the sum of the number of nickel atoms and the number of nickel atoms being 100%. The process is carried out using steps S21 to S25 described later. A ballast source and a nickel source were used. The concentration of nickel was adjusted by adding cobalt in step S21. The nickel concentration is shown when the sum of the number of nickel and nickel atoms is taken as 100%.
[0111] 5(A) and (B) show that the positive electrode active material according to one embodiment of the present invention has a layered rock salt type crystal structure. In the case of cobalt and manganese, the a-axis and c-axis lattice were determined using XRD. The results of estimating the constants are shown below. Figure 5(A) shows the results for the a-axis, and Figure 5(B) shows the results for the c-axis. The XRD used to calculate the lattice constants shown in Figures 5(A) and (B) shows that the positive electrode active material was synthesized The powder after the treatment and before it was incorporated into the positive electrode are shown on the horizontal axis. The manganese concentration is calculated based on the sum of the number of manganese and manganese atoms taken as 100%. The process is carried out using steps S21 to S25 described later. A cobalt source and a manganese source were used. The concentration of manganese was adjusted by adding cobalt in step S21. The manganese concentration is shown when the sum of the number of manganese and manganese atoms is taken as 100%.
[0112] FIG. 4(C) shows the lattice constants of the positive electrode active materials shown in FIG. 4(A) and (B). The lattice constant of the a-axis divided by the lattice constant of the c-axis (a-axis / c-axis) is shown in Fig. 5(C). For the positive electrode active material whose lattice constants are shown in Figures 5(A) and (B), the lattice constants of the a-axis The value is calculated by dividing the number by the lattice constant of the c-axis (a-axis / c-axis).
[0113] Figure 4(C) shows that the a-axis / c-axis tends to change significantly when the nickel concentration is 5% or 7.5%. This distortion is thought to be due to the Jahn-Teller distortion. At nickel concentrations below 7.5%, the Jahn-Teller distortion is small. This suggests that an excellent positive electrode active material can be obtained.
[0114] Next, from FIG. 5(A), when the manganese concentration is 5% or more, the behavior of the change in the lattice constant is This suggests that the Vegard's law is not followed. This suggests that the crystal structure is different. Therefore, the manganese concentration is preferably, for example, 4% or less. It is nice.
[0115] The above nickel and manganese concentration ranges are always within the ranges in the surface layer of the particles. In other words, the surface layer of the particle may have a higher concentration than the above. There are cases.
[0116] From the above, the preferable range of the lattice constant was considered, and it was found that the positive In the active material, the state in which no charge / discharge is performed or the discharge state can be estimated from the XRD pattern. In the layered rock-salt crystal structure of the positive electrode active material particles in the charged state, the lattice constant of the a-axis is 2 .814×10-10 m or larger, 2.817×10 -10 Smaller than m and the c-axis grid Child constant is 14.05 x 10 -10 m or larger, 14.07×10 -10 Smaller than m It has been found that this is preferable. The state in which no charging or discharging is performed is, for example, when preparing a positive electrode for a secondary battery. It may be in a powder state before being mixed.
[0117] Alternatively, the layer structure of the particles of the positive electrode active material in a state where no charge / discharge is performed or in a discharged state may be In a rock-salt crystal structure, the a-axis lattice constant is divided by the c-axis lattice constant (a-axis / c-axis) It is preferable that is greater than 0.20000 and smaller than 0.20049.
[0118] Alternatively, the layer structure of the particles of the positive electrode active material in a state where no charge / discharge is performed or in a discharged state may be In the rock salt crystal structure, when XRD analysis was performed, 2θ was 18.50° or more and 19.30° or less. The first peak is observed at 2θ of 38.00° or less and the second peak is observed at 2θ of 38.00° or more and 38.80° or less. A peak may be observed.
[0119] <XPS> X-ray photoelectron spectroscopy (XPS) measures the surface area at a depth of about 2 to 8 nm (usually about 5 nm). Since it is possible to analyze the area up to about half of the surface layer, the concentration of each element can be determined. It is possible to quantitatively analyze the elements. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is usually about ±1 atomic %, and the detection limit is It depends on the material, but is about 1 atomic %.
[0120] When XPS analysis was performed on the positive electrode active material 100A, the cobalt concentration was set to 1. The relative value of the magnesium concentration is preferably 1.6 to 6.0, and more preferably 1.8 to 4.0. The relative value of the concentration of halogen such as fluorine is preferably 0.2 or more and 6.0 or less. It is preferable that the ratio is 1.2 or more and 4.0 or less.
[0121] For example, monochromated aluminum can be used as the X-ray source when performing XPS analysis. The take-off angle can be set to, for example, 45°.
[0122] In addition, when the positive electrode active material 100A was analyzed by XPS, the bond energy between fluorine and other elements was The peak showing the energy is preferably 682 eV or more and less than 685 eV, and more preferably 684.3 It is more preferable that the bond energy of the lithium fluoride is about 1.5 eV. 685 eV, and the binding energy of magnesium fluoride, 686 eV. In other words, when the positive electrode active material 100A contains fluorine, lithium fluoride and and magnesium fluoride bonds are preferred.
[0123] Furthermore, when the positive electrode active material 100A was analyzed by XPS, the The peak showing the binding energy is preferably 1302 eV or more and less than 1304 eV. It is more preferable that the energy is about 1303 eV. This is a different value from the bond energy of magnesium oxide, which is 1305 eV. In other words, when the positive electrode active material 100A contains magnesium, the magnesium fluoride Preferably, the bond is other than sodium.
[0124] <EDX> Among EDX measurements, the measurement is performed while scanning the area, and the area is evaluated two-dimensionally. This is sometimes called DX surface analysis. Also, data on linear areas is extracted from EDX surface analysis, Evaluating the distribution of atomic concentrations within positive electrode active material particles is sometimes called line analysis.
[0125] EDX surface analysis (e.g. element mapping) revealed that the The concentrations of magnesium and fluorine can be quantitatively analyzed. Line analysis allows the analysis of magnesium and fluorine concentration peaks.
[0126] When EDX analysis was performed on the positive electrode active material 100A, the peak of magnesium concentration in the surface layer The gaps are present up to a depth of 3 nm from the surface to the center of the positive electrode active material 100A. Preferably, the surface is present at a depth of up to 1 nm, more preferably at a depth of up to 0.5 nm. It is even more preferable that
[0127] In addition, the distribution of fluorine in the positive electrode active material 100A overlaps with the distribution of magnesium. Therefore, when EDX analysis is performed, the peak of the fluorine concentration in the surface layer is It is preferable that the surface of the substance 100A is located within a depth of 3 nm toward the center of the substance 100A. It is more preferable that the thickness is within 1 nm, and even more preferable that the thickness is within 0.5 nm. preferable.
[0128] ≪dQ / dVvsV curve≫ In addition, the positive electrode active material of one embodiment of the present invention can be charged at a high voltage and then discharged at a low current of, for example, 0.2 C or less. When discharging at a low rate, a characteristic voltage change may appear near the end of the discharge. The change is in the range of 3.5V to 3.9V in the dQ / dV vs V curve obtained from the discharge curve. This can be clearly seen by the presence of at least one peak.
[0129] [Method 1 for preparing positive electrode active material] Next, an example of a method for manufacturing a positive electrode active material of one embodiment of the present invention will be described with reference to FIGS. Another specific example of the manufacturing method will be described with reference to FIGS.
[0130] <Step S11> As shown in step S11 of FIG. 6, first, a fluorine source and a chlorine source are used as materials for the mixture 902. A halogen source such as a source of fluorine and a magnesium source are prepared. It is also preferable to prepare a lithium source. I wish.
[0131] As the fluorine source, for example, lithium fluoride, magnesium fluoride, etc. can be used. Among them, lithium fluoride has a relatively low melting point of 848°C, and the annealing process described below It is preferred because it is easily melted. Examples of the chlorine source include lithium chloride, magnesium chloride, etc. Examples of magnesium sources that can be used include magnesium fluoride and magnesium oxide. The lithium source may be nesium, magnesium hydroxide, magnesium carbonate, etc. For example, lithium fluoride and lithium carbonate can be used as the lithium fluoride. Lithium can be used as both a lithium source and a fluorine source. Sium can be used both as a fluorine source and as a magnesium source.
[0132] In this embodiment, lithium fluoride LiF is prepared as a fluorine source and a lithium source. Magnesium fluoride (MgF2) will be prepared as a fluorine source and magnesium source. (As a specific example of FIG. 6, step S11 in FIG. 8) Lithium fluoride LiF and magnesium fluoride LiF:MgF2, when mixed at a molar ratio of about 65:35, has a melting point lower than that of LiF. On the other hand, when the amount of lithium fluoride is large, the lithium There is a concern that the amount of lithium fluoride in the battery will be excessive and the cycle characteristics will deteriorate. The molar ratio of F to magnesium fluoride MgF2 is LiF:MgF2=x:1 (0≦x≦1. 9), and LiF:MgF2=x:1 (0.1≦x≦0.5) is more preferable. Preferably, LiF:MgF2=x:1 (x=approximately 0.33) is more preferable. In writing, "nearby" means a value greater than 0.9 times and less than 1.1 times the value.
[0133] If the subsequent mixing and grinding steps are to be carried out in a wet manner, a solvent is prepared. Ketones such as acetone, alcohols such as ethanol and isopropanol, ethers, diethyl ethers, Xanthan, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent which is less likely to react with lithium. In this embodiment, acetone is used (see step S11 in FIG. 8).
[0134] <Step S12> Next, the materials of the mixture 902 are mixed and ground (step S in FIG. 6 and FIG. 8). 12) Mixing can be done either dry or wet, but wet mixing allows for smaller particles to be ground. For mixing, for example, a ball mill, a bead mill, etc. can be used. When using a ball mill, it is preferable to use, for example, zirconia balls as the media. It is preferable to thoroughly mix and grind the mixture 902 to obtain fine powder. .
[0135] <Step S13, Step S14> The mixed and crushed materials are collected (step S13 in FIG. 6 and FIG. 8), and the mixture 90 2 is obtained (step S14 in FIG. 6 and FIG. 8).
[0136] The mixture 902 preferably has a D50 of, for example, 600 nm or more and 20 μm or less. It is more preferable that the particle size is 1 μm or more and 10 μm or less. If it is 2, when it is mixed with a composite oxide having lithium, a transition metal, and oxygen in a later process, In addition, the mixture 902 can be easily adhered uniformly to the surface of the composite oxide particles. If the mixture 902 is uniformly attached to the surface of the composite oxide particles, the mixture will leak onto the surface layer of the composite oxide particles after heating. This is preferable because it is easy to distribute halogen and magnesium in the surface layer. If there is an area that does not contain magnesium, the pseudospinel crystals described above will form in the charged state. It may be difficult to achieve the structure.
[0137] Next, through steps S21 to S25, a catalyst containing lithium, a transition metal, and oxygen is formed. A composite oxide is obtained.
[0138] <Step S21> First, as shown in step S21 of FIG. 6, a compound having lithium, a transition metal, and oxygen is As materials for the composite oxide, a lithium source and a transition metal source are prepared.
[0139] As the lithium source, for example, lithium carbonate, lithium fluoride, etc. can be used.
[0140] The transition metal may be, for example, at least one of cobalt, manganese, and nickel. can be done.
[0141] When using a layered rock salt type crystal structure as the positive electrode active material, the ratio of materials is The mixture ratio of cobalt, manganese, and nickel is the most suitable. Also, the layered rock salt type crystal structure Aluminum may be added to these transition metals within the range where the above can be achieved.
[0142] As the transition metal source, oxides, hydroxides, etc. of the above transition metals can be used. As the cation source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. As the nickel source, manganese oxide, manganese hydroxide, etc. can be used. As the aluminum source, nickel oxide, nickel hydroxide, etc. can be used. , aluminum oxide, aluminum hydroxide, etc. can be used.
[0143] <Step S22> Next, the lithium source and the transition metal source are mixed together (step S22 in FIG. 6). The mixing can be carried out in a dry or wet manner. For example, a ball mill, a bead mill, etc., can be used for mixing. When using a ball mill, for example, zirconia balls can be used as the media. It is preferable to use
[0144] <Step S23> Next, the mixed material is heated. This process is called "sintering" to distinguish it from the subsequent heating process. This is sometimes called the first heating or the formation of the first heat. Heating is usually performed at temperatures between 800°C and 1100°C. It is preferable to perform the treatment at a temperature of 900°C or higher and 1000°C or lower, and more preferable to perform the treatment at about 950°C. If the temperature is too low, the decomposition and melting of the starting materials may be insufficient. On the other hand, if the temperature is too high, the transition metals will be excessively reduced and lithium will evaporate. For example, defects may occur in which cobalt becomes divalent.
[0145] The heating time is preferably from 2 hours to 20 hours. The environment should be kept at a low temperature (for example, a dew point of -50°C or less, preferably -100°C or less). For example, it is preferable to heat at 1000°C for 10 hours, increase the temperature by 200°C / h, and dry. The flow rate of the atmosphere is preferably 10 L / min. The heated material is then cooled to room temperature. For example, the cooling time from a specified temperature to room temperature can be 10 hours or more and 50 hours or more. It is preferable to set it to lower.
[0146] However, cooling to room temperature in step S23 is not essential. 24, if there is a problem in performing steps S25 and S31 to S34 If not, cooling may be to a temperature above room temperature.
[0147] Regarding the metal contained in the positive electrode active material, the above-mentioned steps S22 and S2 A part of the metal may be introduced in steps S41 to S43 described later. It can also be introduced in step S46. More specifically, in steps S22 and S In step S23, metal M1 (M1 is cobalt, manganese, nickel and aluminum) In steps S41 to S46, a metal M2 is introduced. (M2 is, for example, one or more selected from manganese, nickel and aluminum) In this way, by separating the steps of introducing metal M1 and metal M2, In some cases, it may be possible to change the depth profile of the metal. For example, The concentration of metal M2 can be increased in the surface layer of all the layers. The ratio of the number of atoms of the metal M2 to the standard is made higher in the surface layer than in the interior. This can be done.
[0148] In the positive electrode active material according to one embodiment of the present invention, preferably, cobalt is selected as the metal M1, Nickel and aluminum are selected as the metal M2.
[0149] <Step S24, Step S25> The sintered material is collected (step S24 in FIG. 6) and used as the positive electrode active material 100C. A composite oxide containing lithium, a transition metal, and oxygen is obtained (Step S25 in FIG. 6). Specifically, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and cobalt oxide Lithium cobalt oxide partially substituted with manganese, or nickel-manganese-cobalt Lithium oxide is obtained.
[0150] In step S25, the lithium, transition metal, and oxygen that have been synthesized in advance are mixed with In this case, steps S21 to S23 may be used. 24 can be omitted.
[0151] When using a composite oxide containing lithium, a transition metal, and oxygen that has been synthesized in advance In this specification, lithium, transition metals, and and oxygen-containing composite oxide, and the positive electrode active material is mainly composed of lithium, cobalt, Nickel, manganese, aluminum and oxygen are used, and any other elements than the above main components are considered impurities. For example, when analyzed by glow discharge mass spectrometry, the total impurity concentration was 10,000p It is preferably pmwt or less, and more preferably 5000 ppmwt or less. The total impurity concentration of transition metals such as titanium and arsenic is 3000 ppm wt or less. It is preferable that the content of the EDTA be 1500 ppm by weight or less, and more preferable that the content of the EDTA be 1500 ppm by weight or less.
[0152] For example, lithium cobalt oxide (LiCO3) manufactured by Nippon Chemical Industry Co., Ltd. is used as a pre-synthesized lithium cobalt oxide. Lithium cobalt oxide particles (product name: Cellseed C-10N) can be used. The average particle size (D50) of the powder is approximately 12 μm. In the impurity analysis, the magnesium and fluorine concentrations were 50 ppm or less by weight. Calcium concentration, aluminum concentration and silicon concentration are 100 ppm wt or less, nickel concentration The concentration of arsenic is 110 ppm or less, the concentration of sulfur is 500 ppm or less, and the concentration of arsenic is 150 ppm or less. 00 ppm wt or less, and other elements other than lithium, cobalt and oxygen are 150 It is lithium cobalt oxide, which is less than ppm wt.
[0153] Or, lithium cobalt oxide particles (product name: Cellseed C- 5H) can also be used. This has an average particle size (D50) of about 6.5 μm and is In the impurity analysis by -MS, the concentration of elements other than lithium, cobalt and oxygen was C- It is lithium cobalt oxide, which is about the same or less than 10N.
[0154] In this embodiment, cobalt is used as the transition metal, and a previously synthesized cobalt oxide is used. Lithium particles (Cellseed C-10N manufactured by Nippon Chemical Industry Co., Ltd.) will be used (Figure 8).
[0155] The composite oxide having lithium, a transition metal and oxygen in step S25 is formed by removing defects and strain. It is preferable that the crystal structure of the layered rock salt type has few impurities. It is preferable that the composite oxide is a composite oxide having lithium, a transition metal, and oxygen. If there is a high content of impurities, there is a high possibility of a crystal structure with many defects or distortions.
[0156] Here, the positive electrode active material 100C may have cracks. This occurs in any one or more of steps S21 to S25. For example, it occurs during the baking process in step S23. The number of cracks that occur may change depending on conditions such as the speed of the mixture. They may also occur during processes such as mixing and grinding.
[0157] <Step S31> Next, the mixture 902 is mixed with a composite oxide having lithium, a transition metal, and oxygen. (Step S31 in FIG. 6 and FIG. 8). The number of transition metal atoms in the oxide, TM, and the number of magnesium atoms in the mixture 902, MgM The ratio of ix1 is TM:MgMix1=1:y (0.005≦y≦0.05). It is preferable that TM:MgMix1=1:y (0.007≦y≦0.04). It is more preferable that TM:MgMix1=1:0.02 or so.
[0158] The mixing in step S31 is carried out in a manner similar to that in step S12 in order not to destroy the composite oxide particles. For example, the rotation speed is set to be milder than that of the mixing in step S12. It is preferable to use conditions with less heat or shorter time. Also, a dry method is gentler than a wet method. For mixing, a ball mill, a bead mill, etc. can be used. When using a ball mill, for example, zirconia balls should be used as the media. is preferred.
[0159] <Step S32, Step S33> The mixed material is collected (step S32 in FIG. 6 and FIG. 8) to obtain a mixture 903. (Step S33 in FIG. 6 and FIG. 8).
[0160] In this embodiment, the mixture of lithium fluoride and magnesium fluoride is treated with an impurity The present invention describes a method of adding lithium cobalt oxide with low However, the present invention is not limited to this. Instead of the mixture 903 in step S33, a starting material of lithium cobalt oxide may be used. A material containing a magnesium source and a fluorine source and then calcined may be used. The process includes steps S11 to S14 and steps S21 to S25. Since there is no need to separate the steps, the process is simple and highly productive.
[0161] Alternatively, lithium cobalt oxide with magnesium and fluorine added in advance can be used. Magnesium and fluorine doped lithium cobalt oxide can be used to This is simpler and allows the steps up to step S32 to be omitted.
[0162] In addition, lithium cobalt oxide to which magnesium and fluorine have been added in advance was In addition, a magnesium source and a fluorine source may be added.
[0163] <Step S34> Next, the mixture 903 is heated. This step is called annealing to distinguish it from the previous heating step. Or it may be called second heating.
[0164] The annealing is preferably carried out at a suitable temperature and time. The size and the size of the composite oxide particles having lithium, a transition metal and oxygen in step S25 The temperature or composition of the particles varies depending on the conditions. Small particles require lower temperatures or Shorter times may be more preferable.
[0165] For example, if the average particle diameter (D50) of the particles in step S25 is about 12 μm, annealing The temperature is preferably, for example, 600° C. or higher and 950° C. or lower. The annealing time is, for example, 3 hours or longer. It is preferable that the reaction time is 10 hours or more, more preferable that the reaction time is 10 hours or more, and further preferable that the reaction time is 60 hours or more.
[0166] On the other hand, when the average particle diameter (D50) of the particles in step S25 is about 5 μm, the annealing temperature The annealing temperature is preferably, for example, 600° C. to 950° C. The annealing time is, for example, 1 hour to 10 hours. An hour or less is preferable, and about two hours is more preferable.
[0167] The temperature drop time after annealing is preferably, for example, 10 hours or more and 50 hours or less.
[0168] When the mixture 903 is annealed, the material with a low melting point (e.g., fluorine) in the mixture 902 is first melted. It is believed that lithium carbide (lithium carbide, melting point 848°C) melts and distributes in the surface layer of the composite oxide particles. The presence of this molten material then lowers the melting point of other materials, causing them to melt. For example, magnesium fluoride (melting point 1263°C) melts and turns into a composite oxide. It is thought to be distributed in the surface layer of the particles.
[0169] The elements contained in the mixture 902 distributed in the surface layer are lithium, transition metals, and oxygen. It is believed that the metal oxide is dissolved in the complex oxide having the above structure.
[0170] The diffusion of the elements contained in the mixture 902 is more pronounced in the surface and the inside of the composite oxide particles than in the inside of the composite oxide particles. Therefore, magnesium and halogens are concentrated in the surface layer and near the grain boundaries. As will be described later, the magnesium concentration in the surface layer and near the grain boundaries is higher than that in the interior. When the temperature is high, the change in the crystal structure can be more effectively suppressed.
[0171] <Step S35, Step S36> The annealed material is collected (step S35 in FIG. 6 and FIG. 8) to obtain the positive electrode active material 10. 0A_1 is obtained (step S36 in FIG. 6 and FIG. 8).
[0172] [Method 2 for preparing positive electrode active material] The positive electrode active material 100A_1 obtained in step S36 may be subjected to further processing. Here, a process for adding metal Z is performed. This process is performed after step S25. By doing so, the concentration of metal Z in the surface layer of the positive electrode active material particles is made higher than that in the inside. This is preferable because it may be possible to
[0173] The addition of metal Z may be performed, for example, by adding metal Z together with mixture 902 in step S31. In this case, the number of steps can be reduced and the process can be simplified. This is preferable because
[0174] Alternatively, as described below, the addition of metal Z may be performed after steps S31 to S35. In this case, for example, a compound between magnesium and the metal Z can be suppressed. It may be possible to control it.
[0175] Through steps S41 to S53 described below, a positive electrode active material according to one embodiment of the present invention is obtained. In the above process, metal Z is added. The addition of metal Z can be performed, for example, by a liquid phase method such as a sol-gel method, Solid-phase method, sputtering method, deposition method, CVD (chemical vapor deposition) method, PLD (pulsed laser The above-mentioned metal M2 can be added by, for example, This can be done using the metal Z addition step described below.
[0176] <Step S41> As shown in FIG. 7, first, in step S41, a metal source is prepared. When the sol-gel method is applied, a solvent for the sol-gel method is prepared. Metal Z may be aluminum, metal oxide, metal hydroxide, metal oxide, etc. In this case, for example, the number of cobalt atoms in the lithium cobalt oxide is 1, and the metal source is The concentration of aluminum in the metal Z should be between 0.001 and 0.02 times. In the case of Kel, for example, the number of cobalt atoms in lithium cobalt oxide is 1, and the metal source The concentration of nickel in the metal Z is 0.001 times or more and 0.02 times or less. In the case of aluminum and nickel, for example, the cobalt atom of lithium cobalt oxide is The aluminum concentration in the metal source is 0.001 to 0.02 times the concentration of the metal source. In addition, the concentration of nickel in the metal source may be 0.001 times or more and 0.02 times or less.
[0177] As an example, the sol-gel method is used, and aluminum isopropoxy is used as the metal source. An example in which isopropanol is used as a solvent will be shown (Step S41 in FIG. 9).
[0178] <Step S42> Next, aluminum alkoxide is dissolved in alcohol, and then lithium cobalt oxide is added. The particles are mixed (step S42 in FIG. 7 and FIG. 9).
[0179] The amount of metal alkoxide required varies depending on the particle size of lithium cobalt oxide. When using aluminum isopropoxide, the particle size (D50) of lithium cobalt oxide is 20 For the micrometer range, the number of cobalt atoms in lithium cobalt oxide is 1, and the number of aluminum atoms is 1. The aluminum concentration in the isopropoxide is between 0.001 and 0.02 times. It is preferable to add
[0180] Next, the mixture of the alcohol solution of metal alkoxide and the lithium cobalt oxide particles was added to water. Stirring is performed in an atmosphere containing steam. Stirring can be performed, for example, with a magnetic stirrer. The stirring time is determined based on the time required for the water in the atmosphere and the metal alkoxide to undergo hydrolysis and polycondensation reactions. For example, 4 hours, 25°C, 90% RH (relative humidity). It can be performed under conditions of humidity control and relative humidity. and in an atmosphere that is not temperature controlled, such as the air atmosphere in a draft chamber. In such a case, it is preferable to carry out the stirring for a longer period. For example, it may be at room temperature for 12 hours or more.
[0181] By reacting water vapor in the atmosphere with metal alkoxide, the reaction is more efficient than when liquid water is added. The sol-gel reaction can be carried out slowly even at room temperature. This reaction is more efficient than, for example, heating at a temperature above the boiling point of the alcohol solvent. The sol-gel reaction can be carried out slowly. By carrying out the sol-gel reaction slowly, As a result, a coating layer of uniform thickness and good quality can be formed.
[0182] <Step S43, Step S44> After the above treatment, the precipitate is collected from the mixture (step S43 in FIG. 7 and FIG. 9). The recovery method can be filtration, centrifugation, evaporation to dryness, etc. The metal alkoxide can be washed with the same alcohol as that used to dissolve the metal alkoxide. If drying is applied, separation of the solvent and precipitate is not necessary in this step. For example, the precipitate may be collected in the drying step of the next step (step S44). stomach.
[0183] Next, the collected residue is dried to obtain a mixture 904 (step S44 in FIG. 7 and FIG. 9). The drying process can be performed, for example, at 80°C for 1 hour to 4 hours, using vacuum or ventilation. Cut.
[0184] <Step S45> Next, the resulting mixture 904 is fired (step S45 in FIGS. 7 and 9).
[0185] The firing time is preferably 1 hour to 50 hours within the specified temperature range. The baking time is preferably from 2 hours to 20 hours, and more preferably from 2 hours to 20 hours. The crystallinity of the compound containing the metal Z may be low. Alternatively, the diffusion of the metal Z may be insufficient. Or organic matter may remain on the surface. However, if the baking time is long, If the temperature is too high, the diffusion of metal Z may progress too much, resulting in a low concentration in the surface layer and in the vicinity of the grain boundaries. In addition, productivity decreases.
[0186] The specified temperature is preferably 500°C or higher and 1200°C or lower, and more preferably 700°C or higher and 920°C or lower. More preferably, the temperature is 800° C. or higher and 900° C. or lower. The crystallinity of the compound having metal Z formed in the layer may be low. Diffusion may be insufficient, or organic matter may remain on the surface.
[0187] It is also preferable that the firing is carried out in an atmosphere containing oxygen. When the oxygen partial pressure is low, the firing temperature If the temperature is not lowered, there is a risk of Co being reduced.
[0188] In this embodiment, the specified temperature is 850° C. and is maintained for 2 hours. °C / h, and the oxygen flow rate is 10 L / min.
[0189] Regarding cooling after firing, it is preferable to take a long cooling time, since this makes it easier to stabilize the crystal structure. For example, it is preferable that the time required for cooling from a specified temperature to room temperature is 10 hours or more and 50 hours or less. Here, the baking temperature in step S45 is set to be lower than the baking temperature in step S34. Low is preferable.
[0190] <Step S46, Step S47> Next, the cooled particles are collected (step S46 in FIG. 7 and FIG. 9). In the above process, the positive electrode active material 100A according to one embodiment of the present invention is 2 can be fabricated (step S47 in FIG. 7 and FIG. 9).
[0191] After step S47, steps S41 to S46 are repeated. The number of repetitions may be one, or two or more.
[0192] In addition, when the treatment is repeated multiple times, the metal sources used may be the same or different. In the case where a different source is used, for example, an aluminum source is used in the first treatment, A nickel source can be used in the second treatment.
[0193] <Step S51> Next, a compound containing an element X is prepared as a first raw material 901 (see steps in FIGS. 7 and 9). Step S51).
[0194] In step S51, the first raw material 901 may be crushed. A mill, a bead mill, etc. can be used. The powder obtained after pulverization is separated using a sieve. You may also grade it.
[0195] The first raw material 901 is a compound containing an element X. The element X may be phosphorus. The first raw material 901 is preferably a compound having a bond between an element X and oxygen. It is.
[0196] For example, a phosphoric acid compound can be used as the first raw material 901. A phosphoric acid compound having element D can be used as the phosphoric acid. Element D is lithium, sodium , potassium, magnesium, zinc, cobalt, iron, manganese and aluminum It is also possible to use a phosphoric acid compound having hydrogen in addition to element D. In addition, ammonium phosphate and ammonium phosphate with element D can be used as phosphate compounds. A salt of 1,2-dichlorophenyl ether can be used.
[0197] Phosphate compounds include lithium phosphate, sodium phosphate, potassium phosphate, and magnesium phosphate. Nesium, zinc phosphate, aluminum phosphate, ammonium phosphate, lithium dihydrogen phosphate Examples of positive electrode active materials include lithium phosphate, magnesium hydrogen phosphate, and lithium cobalt phosphate. In particular, it is preferable to use lithium phosphate or magnesium phosphate as the acid salt.
[0198] In this embodiment, lithium phosphate is used as the first raw material 901 (see FIGS. 7 and 9). Step S51).
[0199] <Step S52> Next, the first raw material 901 obtained in step S51 and the positive electrode obtained in step S47 are The first raw material 901 is mixed with the active material 100A_2 (step S52 in FIG. 7 and FIG. 9). is 0.01 m for 1 mol of the positive electrode active material 100A_2 obtained in step S25. mol or more and 0.1 mol or less, more preferably 0.02 mol or more and 0.08 mol or less It is preferable to mix the above-mentioned components in an amount of 100% by weight. For the mixing, a ball mill, a bead mill, etc. may be used. The powder obtained after mixing may be classified using a sieve.
[0200] <Step S53> Next, the mixed material is heated (step S53 in FIG. 7 and FIG. 9). In the preparation of the , this step may not be performed. It is preferable to carry out the treatment at a temperature between 00°C and 1200°C, and preferably between 550°C and 950°C. If the temperature is too low, the starting materials may decompose and On the other hand, if the temperature is too high, the transition metals may be excessively reduced. There is a risk of defects occurring due to factors such as lithium evaporation or the like.
[0201] Heating may generate a reaction product between the positive electrode active material 100A_2 and the first raw material 901. do.
[0202] The heating time is preferably from 2 hours to 60 hours. The environment should be kept at a low temperature (for example, a dew point of -50°C or less, preferably -100°C or less). For example, it is preferable to heat at 1000°C for 10 hours, increase the temperature by 200°C / h, and dry. The flow rate of the atmosphere is preferably 10 L / min. The heated material is then cooled to room temperature. For example, the cooling time from a specified temperature to room temperature can be 10 hours or more and 50 hours or more. It is preferable to set it to lower.
[0203] However, cooling to room temperature in step S53 is not essential. If there is no problem in carrying out step 54, cooling may be performed to a temperature higher than room temperature.
[0204] <Step S54> The material thus calcined is collected (step S54 in FIG. 7 and FIG. 9), and a positive electrode having element D is formed. Active material 100A_3 is obtained.
[0205] Regarding the positive electrode active material 100A_1, the positive electrode active material 100A_2, and the positive electrode active material 100A_3, For this purpose, reference can be made to the description of the positive electrode active material 100A given in FIG. 2 and the like.
[0206] (Embodiment 2) In this embodiment, a secondary battery having the positive electrode active material 100 described in the previous embodiment is used. In this embodiment, the positive electrode, the negative electrode, and the electrolyte are A secondary battery in which the electrolyte is enclosed in an exterior body will be taken as an example for explanation.
[0207] [Positive electrode] The positive electrode has a positive electrode active material layer and a positive electrode current collector.
[0208] <Cathode active material layer> The positive electrode active material layer includes at least a positive electrode active material. In addition, other substances such as a coating on the surface of the active material, a conductive additive, or a binder may be included.
[0209] As the positive electrode active material, the positive electrode active material 100 described in the previous embodiment can be used. By using the positive electrode active material 100 described in the above embodiment, the battery has a high capacity and excellent cycle characteristics. Therefore, it is possible to obtain a secondary battery having excellent properties.
[0210] As the conductive assistant, a carbon material, a metal material, a conductive ceramic material, or the like is used. In addition, a fibrous material may be used as the conductive assistant. The content of the conductive additive is preferably 1 wt% or more and 10 wt% or less, and more preferably 1 wt% or more and 5 wt% or less. Below is more preferable.
[0211] The conductive assistant can form an electrically conductive network in the active material layer. The auxiliary agent can maintain the electrical conduction path between the positive electrode active materials. By adding a conductive assistant, it is possible to realize an active material layer having high electrical conductivity. do.
[0212] Examples of the conductive assistant include natural graphite, artificial graphite such as mesocarbon microbeads, carbon Examples of carbon fibers include mesophase pitch carbon fibers. Carbon fibers such as isotropic pitch-based carbon fibers can be used. Carbon nanofibers, carbon nanotubes, etc. can be used. The nanotubes can be produced, for example, by a vapor phase growth method. For example, carbon black (acetylene black (AB) etc.), graphite particles Carbon materials such as graphene and fullerene can be used. Metal powders and fibers such as nickel, aluminum, silver, and gold, as well as conductive ceramic materials, etc. can be used.
[0213] In addition, a graphene compound may be used as the conductive assistant.
[0214] Graphene compounds have excellent electrical properties, including high electrical conductivity, as well as high flexibility and In addition, the graphene may have excellent physical properties such as high mechanical strength. Graphene compounds have a planar shape. Graphene compounds enable surface contact with low contact resistance. In addition, even if the material is thin, it can have very high conductivity, and a small amount can be used efficiently in the active material layer. A conductive path can be formed. Therefore, graphene compounds are used as conductive additives. This is preferable because it is possible to increase the contact area between the active material and the conductive assistant. By using a plate-drying device, the entire surface of the active material is covered with graphene, a conductive additive. It is preferable to form the compound as a coating. In addition, electrical resistance may be reduced. Here, examples of the graphene compound include graphene, multi-graphene, and the like. It is particularly preferred to use RGO, which can be, for example, graphene oxide ( This refers to a compound obtained by reducing graphene oxide (GO).
[0215] When using an active material with a small particle size, for example, 1 μm or less, the specific surface area of the active material Therefore, more conductive paths are required to connect the active materials. Therefore, the amount of the active material carried tends to decrease relatively. If the amount of the conductive additive decreases, the capacity of the secondary battery decreases. When graphene compounds are used, they can efficiently form conductive paths even in small amounts. This is particularly preferable because it is possible to avoid reducing the amount of the active material carried.
[0216] In the following, as an example, a graphene compound is used as a conductive assistant in the active material layer 200. An example of the cross-sectional configuration in this case will be described.
[0217] 10A shows a vertical cross-sectional view of the active material layer 200. The active material layer 200 is made of granular positive electrode active material. A substance 100, a graphene compound 201 as a conductive assistant, a binder (not shown), Here, the graphene compound 201 may be, for example, graphene or multigraphene. Here, the graphene compound 201 preferably has a sheet shape. In addition, the graphene compound 201 may be a multi-graphene or (and) A plurality of graphenes may be partially overlapped to form a sheet.
[0218] In the vertical cross section of the active material layer 200, as shown in FIG. In the portion, the sheet-like graphene compound 201 is dispersed almost uniformly. In this figure, the graphene compound 201 is shown in bold as a schematic diagram, but in reality it is a single layer of carbon molecules. The graphene compounds 201 are each a thin film having a thickness of multiple layers. The positive electrode active material 100 is partially covered, or the positive electrode active material 100 is spread on the surface of the positive electrode active material 100. Since they are formed to be attached to each other, they are in surface contact with each other.
[0219] Here, a plurality of graphene compounds are bonded to each other to form a mesh-like graphene compound. The graphene compound is then bonded to a graphene sheet (hereinafter referred to as a graphene compound net or a graphene net). When the active material is covered with a graphene net, the graphene net can Therefore, the amount of binder can be reduced. Since it is possible to use or not use the active material, the proportion of the active material in the electrode volume and weight can be reduced. The ratio can be improved, that is, the capacity of the secondary battery can be increased.
[0220] Here, graphene oxide is used as the graphene compound 201, and is mixed with an active material to form an active material. After the layer that becomes the graphene layer 200 is formed, it is preferable to reduce the layer. In addition, by using graphene oxide, which has extremely high dispersibility in polar solvents, The compound 201 can be dispersed approximately uniformly inside the active material layer 200. The solvent is removed by evaporation from the dispersion medium containing the graphene oxide dispersed in the solution, and the graphene oxide is reduced. Therefore, the graphene compound 201 remaining in the active material layer 200 partially overlaps with each other. By dispersing the particles so that they come into surface contact with each other, a three-dimensional conductive path can be formed. The reduction of graphene oxide may be performed, for example, by heat treatment or by using a reducing agent. You may go.
[0221] Therefore, unlike granular conductive additives such as acetylene black, which come into point contact with the active material, Since the phenyl compound 201 enables surface contact with low contact resistance, it is not necessary to use a conventional conductive additive. The electrical conductivity between the granular positive electrode active material 100 and the graphene compound 201 can be improved with a smaller amount than that of the graphene compound 201. Therefore, the ratio of the positive electrode active material 100 in the active material layer 200 can be increased. This makes it possible to increase the discharge capacity of the secondary battery.
[0222] In addition, the entire surface of the active material is covered in advance with a spray dryer. The graphene compound is formed as a coating, and the active material is then bonded between the active materials with the graphene compound. A conductive path can also be formed.
[0223] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isopropanol. Acrylonitrile-butadiene rubber, butadiene rubber, ethylene-styrene rubber It is preferable to use a rubber material such as a propylene-diene copolymer. For this purpose, fluororubber can be used.
[0224] As the binder, it is preferable to use, for example, a water-soluble polymer. The molecule may be, for example, a polysaccharide. Chilled cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl Cellulose, diacetyl cellulose, regenerated cellulose and other cellulose derivatives, starch, etc. In addition, these water-soluble polymers can be used in combination with the above-mentioned rubber materials. It is more preferable to use it.
[0225] Alternatively, the binder may be polystyrene, polymethyl acrylate, or polymethacrylate. Methyl (Polymethylmethacrylate, PMMA), Sodium polyacrylate, Polyvinyl chloride Polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyethylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer It is preferable to use materials such as polyvinyl acetate and nitrocellulose.
[0226] The binder may be used in combination of two or more of the above.
[0227] For example, a material having a particularly excellent viscosity adjusting effect may be used in combination with another material. For example, rubber materials have excellent adhesive strength and elasticity, but it is difficult to adjust the viscosity when mixed with a solvent. In such cases, for example, it is possible to mix the material with a particularly excellent viscosity adjusting effect. As a material having a particularly excellent viscosity adjusting effect, for example, a water-soluble polymer is preferably used. In addition, examples of water-soluble polymers that are particularly effective in adjusting viscosity include the above-mentioned polysaccharides, such as cellulose, polysaccharides, and polysaccharides such as cellulose. Carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxy Cellulose derivatives such as dipropyl cellulose, diacetyl cellulose, and regenerated cellulose Conductive materials and starch can be used.
[0228] In addition, cellulose derivatives such as carboxymethyl cellulose are, for example, The solubility of cellulose is increased by converting it into a salt such as sodium salt or ammonium salt. The higher the solubility, the easier it becomes to exert the effect of a viscosity adjuster. It is also possible to improve the dispersibility of the active material and other components when preparing a battery. In the present invention, the cellulose and cellulose derivatives used as the binder of the electrode include: This also includes salts thereof.
[0229] Water-soluble polymers stabilize the viscosity by dissolving in water, and also function as active materials and binders. Other materials that are combined with it, such as styrene butadiene rubber, are stable in aqueous solution. In addition, since it has functional groups, it is easy to stably adsorb onto the surface of the active material. It is expected that cellulose derivatives such as carboxymethyl cellulose can be used. For example, many materials have functional groups such as hydroxyl groups and carboxyl groups. It is expected that the polymers will interact with each other and widely cover the surface of the active material.
[0230] When the binder that covers or contacts the surface of the active material forms a film, it is called a passive film. It is expected that the passive film will act as a barrier against the decomposition of the electrolyte. A film with no electrical conductivity or with very low electrical conductivity, for example, on the surface of an active material When a passive film is formed, it is possible to suppress the decomposition of the electrolyte at the battery reaction potential. In addition, the passive film suppresses electrical conductivity and does not allow lithium ions to be conducted. It is even more desirable to
[0231] <Positive electrode current collector> The positive electrode current collector may be made of metals such as stainless steel, gold, platinum, aluminum, titanium, etc. In addition, the material used for the positive electrode current collector can be made of highly conductive materials such as these alloys. It is preferable that the material does not dissolve at the potential of the positive electrode. Aluminum alloys with added elements such as candium and molybdenum that improve heat resistance It can also be formed from a metal element that reacts with silicon to form a silicide. Metal elements that react with silicon to form silicide include zirconium, Titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten The current collectors are available in foil, plate (sheet), mesh, punched, etc. The current collector may be in the form of a metal, an expanded metal, or the like. It is recommended to use one with a diameter of 5 μm or more and 30 μm or less.
[0232] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer contains a conductive additive and and a binder.
[0233] <Negative electrode active material> As the negative electrode active material, for example, an alloy-based material or a carbon-based material can be used.
[0234] As a negative electrode active material, it can carry out charge and discharge reactions by alloying and dealloying reactions with lithium. Any possible element can be used, for example silicon, tin, gallium, aluminum, Germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. These elements have a low capacity compared to carbon. Silicon has a high theoretical capacity of 4200mAh / g. It is preferable to use silicon, and compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag 3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. Here, charging and discharging are performed by alloying and dealloying reactions with lithium. Elements capable of undergoing a reaction and compounds containing such elements are sometimes called alloy materials. be.
[0235] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO refers to Si O x Here, it is preferable that x has a value close to 1. For example, x can be expressed as: The ratio is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.
[0236] Carbon-based materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Carbon nanotubes, graphene, carbon black, etc. stomach.
[0237] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include meso graphite. Examples include carbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, the MCMB may have a spherical shape, which is preferred. It is relatively easy to reduce the product, which may be preferable. , flake graphite, and spherical natural graphite.
[0238] When lithium ions are inserted into graphite (the formation of lithium-graphite intercalation compounds), ) shows a low potential similar to that of lithium metal (0.05V to 0.3V vs.Li / Li + This allows lithium-ion secondary batteries to exhibit high operating voltages. In addition, graphite has a relatively high capacitance per unit volume, a relatively low volume expansion, and is inexpensive. It is preferable because it has advantages such as higher safety compared to lithium metal.
[0239] In addition, titanium dioxide (TiO2) and lithium titanium oxide (Li4 Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5 ), tungsten oxide (WO2), molybdenum oxide (MoO2), etc. can be done.
[0240] In addition, the negative electrode active material is a composite nitride of lithium and transition metals, which has a Li3N structure. Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2. 6Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 )of This is preferable.
[0241] When a composite nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, In addition, materials that do not contain lithium ions, such as V2O5 and Cr3O8, are used as the positive electrode active material. In addition, when a material containing lithium ions is used as the positive electrode active material, However, by first removing the lithium ions contained in the positive electrode active material, As the lithium-transition metal nitride, a complex nitride of lithium and a transition metal can be used.
[0242] In addition, a material that undergoes a conversion reaction can be used as the negative electrode active material. For example, lithium oxide such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO) A transition metal oxide that does not form an alloy with the metal may be used as the negative electrode active material. Further materials that cause this include Fe2O3, CuO, Cu2O, RuO2, and Cr2O3. Oxides such as CoS 0.89 , NiS, CuS and other sulfides, Zn3N2, Cu3N, Ge Nitrides such as 3N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. This also occurs with fluoride.
[0243] The conductive assistant and binder that the negative electrode active material layer can have are The same materials as the conductive additive and binder that can be used can be used.
[0244] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.
[0245] [Electrolyte] The electrolytic solution contains a solvent and an electrolyte. The solvent for the electrolytic solution is preferably an aprotic organic solvent. Preferable examples include ethylene carbonate (EC), propylene carbonate (PC), Ethylene carbonate, chloroethylene carbonate, vinylene carbonate, gamma-butyro Lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate DEC, Ethyl methyl carbonate (EMC), Methyl formate, Methyl acetate, Ethyl acetate ethyl, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethylsulfate phthalocyanine, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, One of tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.
[0246] In addition, a flame-retardant and non-volatile ionic liquid (room-temperature molten salt) is used as the solvent for the electrolyte. By using one or more, the internal temperature of the secondary battery can be increased due to an internal short circuit or overcharging. Even if the battery is heated, it can prevent explosion or fire of the secondary battery. The electrolyte solution is made of cations and anions. Ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations Aliphatic onium cations such as imidazolium cations and pyridinium cations The aromatic cations are also used as anions in the electrolyte. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl sulfonic acid anion, tetrafluoroborate anion, perfluoroalkyl borate anion phosphate anion, hexafluorophosphate anion, or perfluoroalkyl phosphat ate anion, etc.
[0247] The electrolyte to be dissolved in the above solvent is, for example, LiPF6, LiClO4, L iAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO 4. Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9S O3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2 )2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. One or more of these titanium salts may be used in any combination and ratio. This can be done.
[0248] The electrolyte used in secondary batteries is free of granular waste and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as " It is preferable to use a highly purified electrolyte solution having a low content of impurities. Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less, more preferably 1% or less. It is preferably 0.01% or less.
[0249] In addition, the electrolyte contains vinylene carbonate, propane sultone (PS), and tert-butyl Benzene (TBB), Fluoroethylene carbonate (FEC), Lithium bis(oxa) Lithium borate (LiBOB), as well as dinitriles such as succinonitrile and adiponitrile Additives such as alcohol compounds may be added. The concentration of the additives may be, for example, The content should be between 0.1wt% and 5wt%.
[0250] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.
[0251] By using a polymer gel electrolyte, safety against leakage etc. is improved. The pond can be made thinner and lighter.
[0252] The polymers that can be gelled include silicone gel, acrylic gel, and acrylonitrile gel. , polyethylene oxide gel, polypropylene oxide gel, fluorine-based polymer A gel or the like can be used.
[0253] The polymer may be, for example, a polyalkylene oxide such as polyethylene oxide (PEO). Polymers with side structures, PVDF, polyacrylonitrile, etc., and their For example, a copolymer containing PVDF and hexafluoropropylene ( PVDF-HFP, a copolymer of PVDF and HFP, can be used. The polymer may have a porous shape.
[0254] In addition, instead of the electrolyte solution, a solid electrolyte having an inorganic material such as a sulfide or oxide is used. It is possible to use a solid electrolyte containing a polymer material such as PEO (polyethylene oxide). When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. Since the entire battery can be made solid, there is no risk of leakage, and safety is dramatically improved.
[0255] [Separator] The secondary battery preferably has a separator. Examples of the separator include Paper, nonwoven fabric, glass fiber, ceramics, or nylon (polyamide), vinylon (polyamide) (vinyl alcohol fiber), polyester, acrylic, polyolefin, polyurethane The separator may be made of synthetic fibers or the like. It is preferable that the electrode be processed into a shape and disposed so as to enclose either the positive electrode or the negative electrode.
[0256] The separator may have a multi-layer structure. For example, the separator may be made of an organic material such as polypropylene or polyethylene. The material film is made of ceramic, fluorine, polyamide, or a combination of these. The ceramic material can be, for example, aluminum oxide. Examples of the fluorine-based material include aluminum particles, silicon oxide particles, etc. For example, PVDF, polytetrafluoroethylene, etc. can be used. For example, nylon, aramid (meta-aramid, para-aramid), etc. may be used. can be done.
[0257] Coating with ceramic materials improves oxidation resistance, making it ideal for use as a separator during high-voltage charging and discharging. This suppresses the deterioration of the data and improves the reliability of the secondary battery. Coating the separator and electrodes makes them more easily adhered to each other, improving output characteristics. Coating polyamide materials, especially aramid, improves heat resistance, making them ideal for secondary batteries. Safety can be improved.
[0258] For example, a mixture of aluminum oxide and aramid is coated on both sides of a polypropylene film. Alternatively, the surface of the polypropylene film that comes into contact with the positive electrode may be coated with aluminum oxide. Alternatively, the surface in contact with the negative electrode may be coated with a mixed material of rubber and aramid, and a fluorine-based material may be coated on the surface. .
[0259] By using a multi-layered separator, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin. Since the above-mentioned condition can be maintained, the capacity per unit volume of the secondary battery can be increased.
[0260] [Exterior body] The exterior body of the secondary battery is made of, for example, a metal material such as aluminum or a resin material. Also, a film-like exterior body can be used. , e.g. polyethylene, polypropylene, polycarbonate, ionomer, polyamide On the film made of such materials, highly flexible materials such as aluminum, stainless steel, copper, and nickel are applied. A thin metal film is provided, and a polyamide resin or polyester is further provided on the thin metal film as the outer surface of the exterior body. For example, a film having a three-layer structure including an insulating synthetic resin film such as a terephthalic resin can be used.
[0261] [Charge / discharge method] The secondary battery can be charged and discharged, for example, as follows.
[0262] ≪CC charging≫ First, we will explain CC (constant current) charging as one of the charging methods. A constant current is passed through the secondary battery for the entire period, and charging is stopped when a specified voltage is reached. This is a charging method. The secondary battery is charged with the internal resistance R and the secondary battery capacity C as shown in FIG. Assume that the equivalent circuit is B is the voltage V across the internal resistance R R And two Voltage V applied to the next battery capacity C C It is the sum of.
[0263] During CC charging, the switch is turned on and a constant current is applied, as shown in Figure 11(A). A current I flows through the secondary battery. During this time, the current I is constant, so V R = R x I in ohms According to the law, the voltage V across the internal resistance R R On the other hand, depending on the secondary battery capacity C, Voltage V C increases over time. Therefore, the secondary battery voltage V B Over time, It increases with time.
[0264] and the secondary battery voltage V B When the voltage reaches a certain value, for example 4.3V, charging is stopped. When CC charging is stopped, the switch is turned off and the current I = 0. Therefore, the voltage V applied to the internal resistance RR Therefore, the secondary battery Voltage V B decreases.
[0265] The secondary battery voltage V during CC charging and after CC charging is stopped B and charging current An example of this is shown in FIG. 11(C). The secondary battery voltage V B but ,It is shown that there is a slight decrease after CC charging is stopped.
[0266] ≪CCCV charging≫ Next, we will explain CCCV charging, which is a charging method different from the above. First, charge to a specified voltage using CC charging, then use CV (constant voltage) charging to charge the current This is a charging method in which charging is performed until the current becomes low, specifically until the end current value is reached.
[0267] During CC charging, the constant current power supply is switched on as shown in Figure 12(A). At this time, the constant voltage power supply is switched off and a constant current I flows through the secondary battery. Since I is constant, V R According to Ohm's law, the voltage V across the internal resistance R is R On the other hand, the voltage V applied to the secondary battery capacity C is constant. C increases over time Therefore, the secondary battery voltage V B increases over time.
[0268] and the secondary battery voltage V B When the voltage reaches a certain value, for example 4.3V, the CC charge is stopped. Switch to CV charging. During CV charging, the battery is charged at a constant voltage, as shown in Figure 12(B). The power supply switch is on, the constant current power supply switch is off, and the secondary battery voltage V B is constant On the other hand, the voltage V applied to the secondary battery capacity C C V increases over time. B = V R +V C Therefore, the voltage V across the internal resistance R R becomes smaller over time The voltage V across the internal resistance R R As becomes smaller, V R = R × I by Ohm's law , the current I flowing through the secondary battery also becomes smaller.
[0269] When the current I flowing through the secondary battery becomes a certain current, for example, a current equivalent to 0.01C, When CCCV charging is stopped, all the switches are turned off as shown in Figure 12(C). The switch is turned off and the current I becomes 0. Therefore, the voltage V across the internal resistance R R is 0V However, the voltage V applied to the internal resistance R due to CV charging R is small enough Therefore, even if the voltage drop across the internal resistance R disappears, the secondary battery voltage V B Almost no drop .
[0270] The secondary battery voltage V during CCCV charging and after CCCV charging is stopped B and An example of the charging current is shown in FIG. 13(A). Even if the CCCV charging is stopped, the secondary battery voltage V B Gaho It shows that the aircraft is barely descending at all.
[0271] ≪CC discharge≫ Next, we will explain CC discharge, which is one of the discharge methods. CC discharge is A constant current flows from the secondary battery, and the secondary battery voltage V B to a certain voltage, for example 2.5V. This is a discharge method in which the discharge is stopped when
[0272] The secondary battery voltage V during CC discharge B An example of the discharge current is shown in FIG. As the charge progresses, the secondary battery voltage V B The figure shows how the light descends.
[0273] Next, the discharge rate and the charge rate will be described. This is the relative ratio of the discharge current to the current of the battery, expressed in units of C. In this case, the current equivalent to 1C is X(A). When discharging with a current of 2X(A), C, and if it is discharged at a current of X / 5(A), it is discharged at 0.2C. The charging rate is also the same, and when charging with a current of 2X(A), it is 2C. If it is charged at a current of X / 5(A), it is said to be charged at 0.2C. cormorant.
[0274] (Embodiment 3) In this embodiment, the secondary battery having the positive electrode active material 100 described in the previous embodiment is The material used in the secondary battery described in this embodiment is the same as that in the previous embodiment. The description of the form may be taken into consideration.
[0275] [Coin-type secondary battery] First, an example of a coin-type secondary battery will be described. FIG. 14(A) shows a coin-type (single-layer flat) FIG. 14(B) is a cross-sectional view of a secondary battery of the type shown in FIG.
[0276] The coin-type secondary battery 300 has a positive electrode can 301 that also serves as a positive electrode terminal and a negative electrode can 302 that also serves as a negative electrode terminal. The can 302 is insulated and sealed with a gasket 303 made of polypropylene or the like. The positive electrode 304 is composed of a positive electrode current collector 305 and a positive electrode active material layer 30 provided in contact with the positive electrode current collector. The negative electrode 307 is formed by a negative electrode current collector 308 and a negative electrode current collector 308 are provided so as to be in contact with the negative electrode current collector 308. The negative electrode active material layer 309 is formed by applying a negative electrode active material layer 309 to the negative electrode.
[0277] The positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 are each an active The material layer need only be formed on one side.
[0278] The positive electrode can 301 and the negative electrode can 302 are made of nickel or aluminum, which are resistant to corrosion by the electrolyte. Metals such as titanium, or their alloys or alloys of these with other metals (e.g. stainless steel In order to prevent corrosion by the electrolyte, nickel or aluminum can be used. The positive electrode can 301 is for covering the positive electrode 304, and the negative electrode can 302 is for covering the negative electrode 305. 07 and electrically connect them to each other.
[0279] The negative electrode 307, the positive electrode 304, and the separator 310 are impregnated with an electrolyte, and the negative electrode 307, the positive electrode 304, and the separator 310 are then placed in a vacuum chamber as shown in FIG. As shown in Fig. 2B, the positive electrode can 301 is placed downward, and the positive electrode 304, the separator 310, and the negative electrode 307 are placed in the same position. The positive electrode can 301 and the negative electrode can 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are secured together with a gasket 303. The assembly is then crimped to produce a coin-type secondary battery 300.
[0280] By using the positive electrode active material described in the previous embodiment for the positive electrode 304, it is possible to achieve high capacity and cycle. The coin-type secondary battery 300 can have excellent battery characteristics.
[0281] Here, the flow of current during charging of the secondary battery will be explained with reference to FIG. When a secondary battery is considered as a closed circuit, the movement of lithium ions and the flow of electric current go in the same direction. In secondary batteries that use lithium, the anode and cathode are connected by charging and discharging. The cathode is switched, and the oxidation and reduction reactions are switched, so the reaction potential The electrode with the higher reaction potential is called the positive electrode, and the electrode with the lower reaction potential is called the negative electrode. In this case, even when charging, discharging, or applying a reverse pulse current, Even when a charging current is flowing, the positive electrode is called the "positive electrode" or "+ electrode (plus electrode)" and the negative The electrode is called the "negative electrode" or "-electrode (minus electrode)". The use of the terms anode and cathode in series means that the Therefore, the anode and cathode are not the same. The term "cathode" is not used in this specification. When using the terms positive electrode and negative electrode, specify whether they are being charged or discharged. It will also be indicated whether it corresponds to a positive pole or a negative pole.
[0282] A charger is connected to the two terminals shown in FIG. 14(C) to charge the secondary battery 300. As the charging of the secondary battery 300 progresses, the potential difference between the electrodes increases.
[0283] [Cylindrical secondary battery] Next, let us refer to Figs. 15(A), (B), (C) and (D) for examples of cylindrical secondary batteries. The external appearance of a cylindrical secondary battery 600 is shown in FIG. 15(A). FIG. 15(B) shows 15(B) is a schematic cross-sectional view of a cylindrical secondary battery 600. The cylindrical secondary battery 600 has a positive electrode cap (battery cover) 601 on the top surface and The positive electrode cap and the battery can (external can) 602 are disposed on the bottom surface of the positive electrode cap and the battery can (external can). It is insulated from 602 by a gasket (insulating packing) 610 .
[0284] Inside the hollow cylindrical battery can 602, a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are placed with a separator. The battery element is wound with the battery 605 sandwiched between them. The battery can 602 is closed at one end and open at the other. The battery can 602 is made of nickel, aluminum, or titanium, which is resistant to corrosion by the electrolyte. Metals such as these, or their alloys or alloys of these with other metals (e.g., stainless steel, etc.) In addition, nickel, aluminum, etc. can be used to prevent corrosion by the electrolyte. It is preferable to coat the battery can 602. On the inside of the battery can 602, the positive electrode, the negative electrode, and the The battery element, in which the separator and the battery cell are wound, is sandwiched between a pair of opposing insulating plates 608 and 609. The inside of the battery can 602 in which the battery element is provided is filled with a non-aqueous electrolyte (not shown). The non-aqueous electrolyte can be the same as that used in coin-type secondary batteries. do.
[0285] The positive and negative electrodes used in cylindrical storage batteries are wound, so active material is formed on both sides of the current collector. A positive electrode terminal (positive electrode current collecting lead) 603 is connected to the positive electrode 604, and a negative A negative electrode terminal (negative electrode current collecting lead) 607 is connected to the positive electrode 606. The positive terminal 607 may be made of a metal material such as aluminum. 03 is resistance welded to the safety valve mechanism 612, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 612 is a PTC (Positive Temperature Coefficient) The positive electrode cap 601 is electrically connected to the positive electrode cap 601 via a capacitance 611. The safety valve mechanism 612 is a mechanism for releasing the positive electrode cap 601 when the internal pressure of the battery increases beyond a predetermined threshold. The PTC element 611 cuts off the electrical connection between the positive electrode 604 and the positive electrode 604. It is a thermal resistor element whose resistance increases when the temperature rises, and the amount of current is limited by the increase in resistance. It prevents abnormal heat generation. The PTC element is made of barium titanate (BaTiO3) Semiconductor ceramics and the like can be used.
[0286] 15C, a plurality of secondary batteries 600 are mounted on a conductive plate 613 and a conductive plate 61 4 to form a module 615. The secondary batteries 600 are connected in parallel. They may be connected in series or in parallel and then in series. By configuring a module 615 having a plurality of secondary batteries 600, , a large amount of power can be extracted.
[0287] FIG. 15D is a top view of module 615. For clarity, conductive plate 613 is omitted. As shown in FIG. 15D, the module 615 includes a plurality of secondary batteries 600. The conductive plate may be provided on the conductive wire 616. In addition, even if a temperature control device 617 is provided between multiple secondary batteries 600, When the secondary battery 600 is overheated, the temperature control device 617 cools the secondary battery. If 600 is too cold, it can be heated by the temperature control device 617. Therefore, the performance of the module 615 is less affected by the outside temperature. The heat transfer medium is preferably insulating and non-flammable.
[0288] By using the positive electrode active material described in the above embodiment for the positive electrode 604, a high capacity and cycle can be achieved. The cylindrical secondary battery 600 can have excellent battery characteristics.
[0289] [Example of secondary battery structure] Another structural example of the secondary battery will be described with reference to FIGS.
[0290] 16(A) and 16(B) are diagrams showing the external appearance of a battery pack. The secondary battery 913 has a circuit board 900 and a secondary battery 913. The secondary battery 913 has a label 9 16B, the secondary battery 913 has a terminal 95 1 and terminal 952.
[0291] The circuit board 900 has a circuit 912. The terminal 911 is connected to the terminal The terminal 951 is connected to the terminal 952, the antenna 914, and the circuit 912. Each of the terminals 911 is used as a control signal input terminal, a power supply terminal, etc. This is also fine.
[0292] The circuit 912 may be provided on the back surface of the circuit board 900. The shape of the antenna is not limited to a coil shape, and may be, for example, a wire shape or a plate shape. Antennas such as face antennas, traveling wave antennas, EH antennas, magnetic field antennas, and dielectric antennas A tena may also be used.
[0293] Alternatively, the antenna 914 may be a flat conductor. The flat conductor may have a thickness of 100 .mu.m or less for electric field coupling. In other words, the capacitor can function as one of the two conductors. The antenna 914 may function as one of the conductors. In addition, it is also possible to exchange power using an electric field.
[0294] The battery pack has a layer 916 between the antenna 914 and the secondary battery 913. Layer 916 has a function of blocking an electromagnetic field generated by, for example, a secondary battery 913. For example, a magnetic material can be used as 6.
[0295] The structure of the secondary battery is not limited to that shown in FIGS.
[0296] For example, as shown in Figs. 17(A1) and 17(A2), Figs. In the secondary battery 913 shown in FIG. 9B, an antenna may be provided on each of a pair of opposing surfaces. FIG. 17(A1) is an external view showing one of the pair of surfaces, and FIG. 17(A2) is an external view showing one of the pair of surfaces. 16(A) and 16(B) are external views showing the other of the pair of surfaces. For the same parts as the secondary battery, please refer to the description of the secondary battery shown in Figs. 16(A) and 16(B). It can be used as appropriate.
[0297] As shown in FIG. 17(A1), a layer 916 is sandwiched between one of the pair of surfaces of a secondary battery 913. As shown in FIG. 17(A2), an antenna 914 is provided on both sides of the secondary battery 913. An antenna 918 is provided on the opposite side of the layer 917. The layer 917 is, for example, a secondary battery 913. The layer 917 has a function of blocking the electromagnetic field caused by the magnetic field. It can be used.
[0298] By adopting the above structure, the size of both the antenna 914 and the antenna 918 can be increased. The antenna 918 can perform data communication with an external device, for example. The antenna 918 has a function of being applicable to the antenna 914, for example. A method for communicating between a secondary battery and other devices via an antenna 918 can be used. The method is to use NFC (near field communication) between secondary batteries and other devices. It is possible to apply a response method that allows the user to respond to a request.
[0299] Alternatively, as shown in FIG. 17(B1), the secondary battery 9 shown in FIG. 16(A) and FIG. 16(B) may be used. A display device 920 may be provided in the display device 13. The display device 920 is electrically connected to the terminal 911. It is not necessary to provide the label 910 in the portion where the display device 920 is provided. 16(A) and 16(B), the same parts as those of the secondary battery shown in FIG. The description of the secondary battery shown in FIG. 16(B) can be used as appropriate.
[0300] The display device 920 displays, for example, an image indicating whether charging is in progress, an image indicating the amount of stored power, etc. The display device 920 may be, for example, an electronic paper, a liquid crystal display device, an electronic For example, electroluminescence (EL) display devices can be used. By using the polarizer, the power consumption of the display device 920 can be reduced.
[0301] Alternatively, as shown in FIG. 17(B2), the secondary battery 9 shown in FIG. 16(A) and FIG. 16(B) may be used. A sensor 921 may be provided on the sensor 13. The sensor 921 is connected to the terminal 911 via a terminal 922. Electrically connected to the secondary battery shown in FIG. 16(A) and FIG. In this regard, the description of the secondary battery shown in FIG. 16(A) and FIG. 16(B) can be appropriately used.
[0302] The sensor 921 may be, for example, a sensor for detecting displacement, position, velocity, acceleration, angular velocity, number of rotations, distance, Light, liquid, magnetism, temperature, chemicals, sound, time, hardness, electric field, current, voltage, power, radiation, It is sufficient if it has the function of measuring flow rate, humidity, gradient, vibration, odor, or infrared. By providing the sensor 921, for example, data indicating the environment in which the secondary battery is placed can be obtained. It is also possible to detect data (such as temperature) and store it in memory within the circuit 912.
[0303] Further, a structural example of the secondary battery 913 will be described with reference to FIGS. 18(A), 18(B) and 19. Reveal.
[0304] A secondary battery 913 shown in FIG. 18A has a terminal 951 and a terminal 952 inside a housing 930. The winding body 950 is impregnated with an electrolyte inside the housing 930. The terminal 952 is in contact with the housing 930, and the terminal 951 is in contact with the housing 930 by using an insulating material or the like. It is not in contact with the housing 930. For convenience, the housing 930 is shown in FIG. 18(A). However, in reality, the winding body 950 is covered by the housing 930, and the terminals 951 and 52 extends outside the housing 930. The housing 930 is made of a metal material (e.g., aluminum For example, a material such as aluminum or a resin material can be used.
[0305] As shown in FIG. 18B, the housing 930 shown in FIG. 18A may be made of a plurality of materials. For example, the secondary battery 913 shown in FIG. 18B may be formed by a housing 930a and a housing The wound body is placed in the area surrounded by the housing 930a and the housing 930b. 950 is provided.
[0306] The housing 930a can be made of an insulating material such as organic resin. By using a material such as organic resin on the surface on which the nanotube is formed, the electric field generated by the secondary battery 913 If the electric field shielding by the housing 930a is small, the housing 930a Antennas such as antenna 914 and antenna 918 may be provided inside the housing 930b. For example, a metal material can be used.
[0307] Further, the structure of the wound body 950 is shown in FIG. The winding body 950 has a positive electrode 932 and a separator 933. Then, the negative electrode 931 and the positive electrode 932 are stacked on top of each other, and the laminated sheet is wound. The negative electrode 931, the positive electrode 932, and the separator 933 are further laminated. Multiple layers may be stacked.
[0308] The negative electrode 931 is connected to the terminal 951 or the terminal 952 as shown in FIG. The positive electrode 932 is connected to the terminal 951 or the other terminal 952. It is connected to the terminal 911 shown in FIGS.
[0309] By using the positive electrode active material described in the above embodiment for the positive electrode 932, a high capacity and cycle can be achieved. This results in a secondary battery 913 with excellent battery characteristics.
[0310] [Laminated secondary battery] Next, examples of laminated secondary batteries will be described with reference to FIGS. 20(A) to 26(B). If the laminated secondary battery has a flexible structure, it can be used as a flexible battery. If the secondary battery is mounted on an electronic device having at least a part of the battery, the secondary battery can be adapted to the deformation of the electronic device. It can also be bent.
[0311] 20(A), (B) and (C) are used to explain the laminated secondary battery 980. The laminated secondary battery 980 has a wound body 993 shown in FIG. The wound body 993 includes a negative electrode 994, a positive electrode 995, and a separator 996. The winding body 993 is a winding body 993 in which a separator 996 is sandwiched between the negative electrode 991 and the winding body 950 as described with reference to FIG. The positive electrode 994 and the positive electrode 995 are stacked on top of each other, and the laminated sheet is wound up.
[0312] The number of layers of the negative electrode 994, the positive electrode 995, and the separator 996 may be as large as necessary. The negative electrode 994 is connected to the lead electrode 997 and the The positive electrode 995 is connected to a negative electrode collector (not shown) via one of the leads 998. The other of the electrode 997 and the lead electrode 998 is connected to a positive electrode collector (not shown). .
[0313] As shown in FIG. 20B, a film 981 that serves as an exterior body and a film 982 having a recess are The above-mentioned wound body 993 is housed in the space formed by bonding the above-mentioned wound body 993 and the above-mentioned wound body 993 together by thermocompression bonding or the like. By this, a secondary battery 980 can be manufactured as shown in FIG. 93 has a lead electrode 997 and a lead electrode 998, a film 981, and a recess. The inside of the film 982 is impregnated with an electrolyte.
[0314] The film 981 and the film 982 having the recesses are made of a metal material such as aluminum. The film 981 and the film 982 having the recesses can be made of a metal or resin material. If a resin material is used as the material for the recess 981, when an external force is applied, the recess 981 and the film 982 are The film 982 having the above structure can be deformed to produce a flexible storage battery. can be done.
[0315] In addition, although Fig. 20(B) and Fig. 20(C) show examples using two films, A space is formed by folding one sheet of film, and the above-mentioned wound body 9 is inserted into the space. 93 may also be accommodated.
[0316] By using the positive electrode active material described in the previous embodiment for the positive electrode 995, it is possible to achieve high capacity and cycle. It is possible to obtain a secondary battery 980 having excellent battery characteristics.
[0317] In addition, in Fig. 20(B) and (C), the film is wound in a space formed by the exterior body. An example of the secondary battery 980 having a body has been described. For example, in FIG. In this way, multiple rectangular positive electrodes, separators, and The battery may be a secondary battery having a cathode and an anode.
[0318] The laminated secondary battery 500 shown in FIG. 21(A) includes a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a material layer 502, a negative electrode current collector 504 and a negative electrode active material layer 505 The battery includes a negative electrode 506, a separator 507, an electrolyte 508, and an exterior body 509. A separator 507 is provided between a positive electrode 503 and a negative electrode 506 provided in a housing 509. The exterior body 509 is filled with an electrolyte 508. The electrolyte 508 contains The electrolyte solution shown in the second embodiment can be used.
[0319] In the laminated secondary battery 500 shown in FIG. 21(A), a positive electrode current collector 501 and The negative electrode current collector 504 also serves as a terminal for obtaining electrical contact with the outside. A part of the electrode current collector 501 and the negative electrode current collector 504 is exposed to the outside from the exterior body 509. The positive electrode current collector 501 and the negative electrode current collector 504 may be disposed in the outer casing 509. The lead electrode is connected to the positive electrode current collector 501 or the negative electrode current collector 502 by using a lead electrode. The lead electrode may be exposed to the outside by ultrasonic bonding to the electrode current collector 504 .
[0320] In the laminated secondary battery 500, the exterior body 509 is made of, for example, polyethylene, polypropylene, On a membrane made of a material such as polypropylene, polycarbonate, ionomer, polyamide, etc. A thin metal film with excellent flexibility, such as aluminum, stainless steel, copper, or nickel, is applied. On the metal thin film, an insulating composite such as polyamide resin or polyester resin is applied as the outer surface of the exterior body. A laminate film having a three-layer structure provided with a resin film can be used.
[0321] An example of the cross-sectional structure of a laminated secondary battery 500 is shown in FIG. For simplicity, (A) shows an example of a structure with two current collectors. ) it is composed of multiple electrode layers.
[0322] In FIG. 21B, as an example, the number of electrode layers is 16. In FIG. 21(B), the negative electrode current collector 504 is made up of eight layers. 21(B) shows a structure of 16 layers in total, with the positive electrode current collector 501 being 8 layers. The cross section of the extraction part is shown, and eight layers of negative electrode current collector 504 are ultrasonically bonded. Of course, the number of electrode layers is not limited to 16, and may be more or less. In this case, a secondary battery having a larger capacity can be obtained. In this case, a secondary battery can be made thin and has excellent flexibility.
[0323] An example of the external appearance of a laminated secondary battery 500 is shown in FIGS. 22 and 23 show a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead The positive electrode 510 and the negative electrode 511 are connected to each other.
[0324] FIG. 24(A) shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 is connected to a positive electrode current collector 5 01, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The electrode 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). The electrode 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 is formed in a region where the negative electrode current collector 504 is partially exposed, that is, a tab. The area and shape of the tab regions of the positive electrode and the negative electrode are as shown in the example of FIG. Not limited.
[0325] [Method of manufacturing laminated secondary battery] Here, an example of a method for producing a laminated secondary battery, the external view of which is shown in FIG. This will be explained using 4(B) and (C).
[0326] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. The negative electrode 506, the separator 507, and the positive electrode 503 are shown. Next, the bonding of the tab regions of the positive electrode 503 and the bonding of the tabs of the positive electrode on the outermost surface are shown. The positive electrode lead electrode 510 is bonded to the substrate region. For example, ultrasonic welding or the like is used for the bonding. Similarly, the tab regions of the negative electrodes 506 are joined to each other, and the negative electrode is attached to the tab region of the outermost negative electrode. The lead electrode 511 is joined.
[0327] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .
[0328] Next, as shown in FIG. 24(C), the exterior body 509 is folded at the portions indicated by the dashed lines. After that, the outer periphery of the exterior body 509 is bonded. For example, thermocompression bonding may be used for bonding. In order to fill the electrolyte 508 later, a part (or one side) of the exterior body 509 is In this case, a region that is not joined to the substrate (hereinafter referred to as an inlet) is provided.
[0329] Next, electrolyte 508 (not shown) is introduced into the exterior body 509 through an inlet. The electrolyte 508 is introduced into the inside of the electrode 509 under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is bonded. A secondary battery 500 of this type can be fabricated.
[0330] By using the positive electrode active material described in the previous embodiment for the positive electrode 503, a high capacity and cycle This results in a secondary battery 500 with excellent battery characteristics.
[0331] [Bendable secondary battery] Next, examples of bendable secondary batteries are shown in Figs. 25(A), (B1), and (B2). (C), (D), and (B) of FIG.
[0332] FIG. 25(A) shows a schematic top view of a bendable secondary battery 250. 1), (B2), and (C) are cut along the lines C1-C2 and C3 in FIG. 25(A), respectively. 1C-C4 is a schematic cross-sectional view taken along line A1-A2. The positive electrode 211a and the negative electrode 211b are housed inside the exterior body 251. A lead 212a electrically connected to the negative electrode 211b and a lead 212b electrically connected to the negative electrode 211b are connected to the negative electrode 211c. The lead 212b extends outside the exterior body 251. In addition to the positive electrode 211a and the negative electrode 211b, an electrolyte (not shown) is enclosed in the positive electrode 211a. do.
[0333] The positive electrode 211a and the negative electrode 211b of the secondary battery 250 are shown in FIG. FIG. 26(A) shows a positive electrode 211a, a negative electrode 211b, and a separator. FIG. 26(B) is a perspective view illustrating the stacking order of the positive electrode 211a and the negative electrode 214. 11b, as well as leads 212a and 212b.
[0334] As shown in FIG. 26(A), the secondary battery 250 includes a plurality of rectangular positive electrodes 211a, a plurality of The negative electrode 211b has a rectangular shape and a plurality of separators 214. Each of the positive electrodes 211a and 211b has a protruding tab portion and a portion other than the tab. A positive electrode active material layer is formed on the portion of the negative electrode 211b other than the tab on the other surface of the negative electrode 211b. A negative electrode active material layer is formed on the portion.
[0335] The surfaces of the positive electrodes 211a on which the positive electrode active material layer is not formed and the surfaces of the negative electrodes 211b on which the negative electrode active material layer is not formed are The positive electrode 211a and the negative electrode 211b are laminated so that the surfaces on which no material is formed are in contact with each other. will be done.
[0336] In addition, the surface of the positive electrode 211a on which the positive electrode active material is formed and the surface of the negative electrode 211b on which the negative electrode active material is formed are A separator 214 is provided between the faces. The parameter 214 is shown in dotted line.
[0337] As shown in FIG. 26B, the positive electrodes 211a and the leads 212a are connected to each other at the joints 21. The negative electrodes 211b and the leads 212b are electrically connected to each other at the joints 5a. Electrical connection is made at 215b.
[0338] Next, the exterior body 251 will be described with reference to FIGS. 25(B1), (B2), (C), and (D). do.
[0339] The exterior body 251 has a film-like shape and is arranged to sandwich the positive electrode 211a and the negative electrode 211b. The exterior body 251 is folded in two as shown in FIG. The pair of sealing portions 262 includes the positive electrode 211a and the sealing portion 263. The negative electrode 211b is sandwiched between the seal portions 211b and 211c, and may also be called side seals. 63 has a portion overlapping with the lead 212a and the lead 212b, and is also called a top seal. It is possible.
[0340] The exterior body 251 has ridge lines 271 and valley lines 272 at the portions overlapping the positive electrode 211a and the negative electrode 211b. It is preferable that the sealing portion 272 of the exterior body 251 has a corrugated shape in which the sealing portions 272 are arranged alternately. 62 and seal portion 263 are preferably flat.
[0341] FIG. 25(B1) is a cross section cut at the portion overlapping with the ridge line 271, and FIG. 25(B2) is 25(B1) and (B2) are cross sections cut at the part where the valley line 272 overlaps. It corresponds to a cross section in the width direction of the secondary battery 250, the positive electrode 211a, and the negative electrode 211b.
[0342] Here, the ends in the width direction of the positive electrode 211a and the negative electrode 211b, i.e., the positive electrode 211a and The distance between the end of the negative electrode 211b and the seal portion 262 is defined as La. When the electrode is bent or deformed to the axial direction, the positive electrode 211a and the negative electrode 211b are In this case, if the distance La is too short, the exterior body 251 The positive electrode 211a and the negative electrode 211b may rub strongly against each other, and the exterior body 251 may be damaged. In particular, when the metal film of the exterior body 251 is exposed, the metal film is easily damaged by the electrolyte. Therefore, it is preferable to set the distance La as long as possible. On the other hand, if the distance La is made too large, the volume of the secondary battery 250 increases. .
[0343] In addition, the greater the total thickness of the laminated positive electrodes 211a and negative electrodes 211b, the greater the It is preferable to increase the distance La between the negative electrode 211a and the seal portion 262. stomach.
[0344] More specifically, the positive electrode 211a and the negative electrode 211b are stacked together, and a separator (not shown) is When the total thickness of the actuator 214 is t, the distance La is 0.8 to 3.0 times the thickness t. or less, preferably 0.9 to 2.5 times, more preferably 1.0 to 2.0 times By setting the distance La in this range, the device is compact and has good resistance to bending. This makes it possible to realize a highly reliable battery.
[0345] In addition, when the distance between the pair of seal portions 262 is a distance Lb, the distance Lb is a and the width of the negative electrode 211b (here, the width Wb of the negative electrode 211b). This is preferable when the secondary battery 250 is repeatedly bent or deformed. Even if the positive electrode 211a and the negative electrode 211b come into contact with the exterior body 251, Since a part of the negative electrode 211b can be shifted in the width direction, the positive electrode 211a and the negative electrode 211 This effectively prevents the outer casing 251 from rubbing against the outer casing 251.
[0346] For example, the difference between the distance Lb between the pair of seal portions 262 and the width Wb of the negative electrode 211b is The thickness t of the electrode 211a and the negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 times or less. It is preferable that the ratio is 2.0 times or more and 5.0 times or less, and more preferably 2.0 times or more and 4.0 times or less. stomach.
[0347] In other words, it is preferable that the distance Lb, the width Wb, and the thickness t satisfy the relationship of the following formula 1. I wish.
[0348]
number
[0349] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, and more preferably Most of the time, the ratio is between 1.0 and 2.0.
[0350] FIG. 25C is a cross section including the lead 212a, and shows the secondary battery 250, the positive electrode 211, a and the cross section of the negative electrode 211b in the longitudinal direction. At the end portion 261, the ends of the positive electrode 211a and the negative electrode 211b in the length direction and the exterior body 25 It is preferable to have a space 273 between the first and second electrodes 271 and 272.
[0351] FIG. 25(D) shows a schematic cross-sectional view of the secondary battery 250 when it is bent. ) corresponds to the cross section taken along line B1-B2 in FIG. 25(A).
[0352] When the secondary battery 250 is bent, a part of the exterior body 251 located on the outside of the bend stretches and More specifically, the other part located on the outside of the exterior body 251 is deformed so as to shrink. The part where the wave is generated is deformed so that the amplitude of the wave becomes small and the period of the wave becomes large. The part located inside 251 changes so that the wave amplitude is large and the wave period is small. In this way, the exterior body 251 is deformed, and the exterior body 251 is bent. Since this stress is alleviated, the material that constitutes exterior body 251 itself does not need to expand or contract. As a result, the exterior body 251 is not damaged and the secondary battery 250 can be bent with a small force. can.
[0353] Furthermore, as shown in FIG. 25(D), when the secondary battery 250 is bent, the positive electrode 211a and the negative electrode At this time, the plurality of stacked positive electrodes 211a and The negative electrode 211b is fixed at one end on the seal portion 263 side by the fixing member 217, so that it is not broken. The amount of deviation increases toward the bent portion 261. The stress applied to the positive electrode 211a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211 As a result, the positive electrode 211a and the negative electrode 211b are not damaged. Therefore, the secondary battery 250 can be bent without any trouble.
[0354] In addition, a space 273 is provided between the positive electrode 211a and the negative electrode 211b and the exterior body 251. As a result, the positive electrode 211a and the negative electrode 211b located on the inner side when bent are attached to the exterior body 25 It can move relative to 1 without touching it.
[0355] Examples are shown in Figures 25(A), (B1), (B2), (C), (D), and Figures 26(A) and (B). The secondary battery 250 shown in FIG. 1 was repeatedly bent and stretched without any damage to the exterior body or any damage to the positive electrode 211a. In addition, the negative electrode 211b is less likely to be damaged, and the battery characteristics are less likely to deteriorate. The positive electrode 211a of the battery 250 is made of the positive electrode active material described in the previous embodiment. This makes it possible to obtain a battery with even better cycle characteristics.
[0356] (Embodiment 4) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on an electronic device will be described. Reveal.
[0357] First, as described in part of the third embodiment, a bendable secondary battery is mounted on an electronic device. Examples of such a battery using a bendable secondary battery are shown in Fig. 27(A) to Fig. 27(G). As a child device, for example, a television device (also called a television or television receiver) , computer monitors, digital cameras, digital video cameras, digital photo frame, mobile phone (also called mobile phone or mobile phone device), portable game machine, portable information Examples of such devices include information terminals, audio playback devices, and large game machines such as pachinko machines.
[0358] In addition, the secondary battery having a flexible shape can be attached to the inner or outer walls of a house or a building, or to an automobile. It can also be incorporated into curved interior or exterior surfaces of a vehicle.
[0359] FIG. 27A shows an example of a mobile phone. A mobile phone 7400 includes a housing 740. In addition to the display unit 7402 incorporated in the 1, the operation buttons 7403, the external connection port 7404, The mobile phone 7400 is equipped with a speaker 7405, a microphone 7406, and the like. The secondary battery 7407 is a secondary battery according to one embodiment of the present invention. This makes it possible to provide a lightweight mobile phone with a long life.
[0360] FIG. 27B shows the mobile phone 7400 in a curved state. When the 00 is deformed by an external force and curved, the secondary The secondary battery 7407 is also bent. At this time, the state of the bent secondary battery 7407 is as shown in FIG. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is bent. The secondary battery 7407 is fixed in a state in which the lead electrode is electrically connected to the current collector. For example, the current collector is made of copper foil, and some of it is alloyed with gallium to form a contact with the current collector. This improves adhesion to the active material layer, making the secondary battery 7407 highly reliable when bent. It is composed of:
[0361] FIG. 27D shows an example of a bangle-type display device. The portable display device 7100 is 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 27(E) shows the bent state of the secondary battery 7104. When the device is bent and worn on the user's arm, the case may deform and cause damage to part of the secondary battery 7104 or The total curvature changes. The degree of curvature at any point on the curve is expressed as the radius of the corresponding circle. The value expressed as the radius of curvature is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. A part of the main surface of the case or secondary battery 7104 within the range of 40 mm to 150 mm in diameter Or the entire surface of the secondary battery 7104 changes. If the thickness is within the range of 0 mm or less, high reliability can be maintained. By using the secondary battery of one embodiment of the present invention, a lightweight portable display device with a long life can be provided.
[0362] FIG. 27F shows an example of a wristwatch-type portable information terminal. The housing 7201, the display unit 7202, the band 7203, the buckle 7204, the operation button 7 205, an input / output terminal 7206, etc.
[0363] The portable information terminal 7200 is capable of carrying out mobile phone calls, e-mails, viewing and creating documents, playing music, and internet connections. It can run various applications such as internet communication and computer games. Cut.
[0364] The display unit 7202 has a curved display surface, and displays information along the curved display surface. The display unit 7202 is equipped with a touch sensor, and the screen can be operated by touching it with a finger or a stylus. For example, the icon 7 displayed on the display unit 7202 can be operated by touching the By touching 207, the application can be launched.
[0365] The operation button 7205 is used to set the time, turn the power on and off, and turn wireless communication on and off. It supports various functions such as auto-start, silent mode and power saving mode. For example, an operating system built into the portable information terminal 7200 can be Depending on the system, the functions of the operation buttons 7205 can be freely set.
[0366] In addition, the mobile information terminal 7200 is capable of performing short-distance wireless communication according to a communication standard. For example, by communicating with a wireless headset, a hands-free You can also make calls.
[0367] The portable information terminal 7200 also includes an input / output terminal 7206 and is connected to other information terminals via a connector. Data can be exchanged directly through the input / output terminal 7206. The charging operation can be performed by wireless power supply without going through the input / output terminal 7206. You may go.
[0368] The display portion 7202 of the portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a lightweight and long-life portable information terminal can be provided. For example, the secondary battery 7104 shown in FIG. 27E is curved and inserted into the housing 7201. The flexible support 7204 may be incorporated in a flexible state or inside the band 7203 in a bendable state.
[0369] The portable information terminal 7200 preferably has a sensor. For example, a fingerprint sensor may be used as the sensor. Human body sensors such as sensors for measuring body temperature, touch sensors, pressure sensors, and acceleration sensors. It is preferable that the sensor, etc. be mounted.
[0370] FIG. 27G shows an example of a wristband-type display device. The display device 7300 has a display unit The display device 7300 includes a secondary battery of one embodiment of the present invention. The display portion 7304 may be provided with a touch sensor, and may function as a portable information terminal. It is also possible.
[0371] The display surface of the display unit 7304 is curved, and the display is performed along the curved display surface. In addition, the display device 7300 can display the image by short-distance wireless communication according to a communication standard. You can change the situation.
[0372] The display device 7300 also has an input / output terminal, and can directly connect to other information terminals via a connector. It is possible to exchange data. It is also possible to charge the device via the input / output terminal. The charging operation may be performed by wireless power supply without using the input / output terminals.
[0373] When the secondary battery of one embodiment of the present invention is used as the secondary battery included in the display device 7300, It is possible to provide a lightweight, long-life display device.
[0374] In addition, an example in which the secondary battery with excellent cycle characteristics shown in the above embodiment is mounted on an electronic device will be described. This will be explained using Figures 27(H), 28(A), (B), (C) and 29.
[0375] By using the secondary battery of one embodiment of the present invention as a secondary battery in everyday electronic devices, the battery can be lightweight and have a long life. We can provide products that are useful for daily use. For example, electric toothbrushes, electric shavers, Examples of such products include electric beauty devices. The secondary batteries used in these products are Therefore, there is a demand for a secondary battery that is stick-shaped, small, lightweight, and has a large capacity.
[0376] FIG. 27(H) is a perspective view of a device also called a tobacco-containing smoking device (electronic cigarette). In FIG. 27(H), an electronic cigarette 7500 includes an atomizer 7501 that includes a heating element and an The secondary battery 7504 that supplies power to the tomizer and the car including the liquid supply bottle and the sensor are To enhance safety, the secondary battery 7504 is protected from overcharging and other A protection circuit for preventing over-discharge may be electrically connected to the secondary battery 7504. The secondary battery 7504 has an external terminal so that it can be connected to a charging device. The 7504 is the tip when held, so the total length is short and the weight is light. It is desirable that the secondary battery according to one embodiment of the present invention has a high capacity and good cycle characteristics. The 7500 is a small, lightweight electronic cigarette that can be used for long periods of time. We can provide it.
[0377] Next, FIG. 28(A) and FIG. 28(B) show an example of a foldable tablet terminal. The tablet terminal 9600 shown in FIG. 28(A) and FIG. 28(B) includes a housing 963. 0a, a housing 9630b, a movable part 9640 connecting the housings 9630a and 9630b, A display unit 9631 having a display unit 9631a and a display unit 9631b, switches 9625 to The display unit 9631 has a switch 9627, a fastener 9629, and an operation switch 9628. By using a flexible panel, the tablet terminal has a larger display area. FIG. 28(A) shows a tablet terminal 9600 in an open state. (B) shows the tablet terminal 9600 in a closed state.
[0378] The tablet terminal 9600 also includes a housing 9630a and a housing 9630b. The power storage unit 9635 is connected to the housing 9630a through the movable portion 9640. It is provided across the body 9630b.
[0379] The display unit 9631 can be configured such that all or a part of the display unit 9631 is a touch panel. By touching images, text, input forms, etc. that contain icons displayed in the relevant area, data is For example, a keyboard is provided on the entire surface of a display portion 9631a on the housing 9630a side. By displaying the board button, information such as characters and images can be displayed on the display unit 9631b on the housing 9630b side. The information may be displayed.
[0380] In addition, a keyboard is displayed on the display unit 9631b on the housing 9630b side. The display unit 9631a on the a side may be used to display information such as text and images. A touch panel keyboard display switching button is displayed on the part 9631. By touching the buttons with your finger or a stylus, a keyboard will be displayed on the display 9631. It may also be.
[0381] In addition, the touch panel area of the display unit 9631a on the housing 9630a side and the touch panel area of the display unit 9631b on the housing 9630b side It is also possible to simultaneously perform touch input to the touch panel area of the display portion 9631b.
[0382] In addition, the switches 9625 to 9627 are used to operate the tablet terminal 9600. It is not only an interface for the For example, at least one of the switches 9625 to 9627 may be an interface. The other functions as a power on / off switch for the Tablet 9600. Also, for example, at least one of the switches 9625 to 9627 may be The ability to switch between portrait and landscape display orientation, or between black and white and color display For example, at least one of the switches 9625 to 9627 may have a function of changing the At least one of the display units 9631 may have a function of adjusting the luminance of the display unit 9631. The brightness of 31 is the brightness during use detected by a light sensor built into the tablet terminal 9600. The tablet device can be optimized according to the amount of external light. In addition, it also incorporates other detection devices such as gyros, acceleration sensors, and other sensors that detect tilt. It may be stored.
[0383] In FIG. 28A, a display portion 9631a on the housing 9630a side and a display portion 9631b on the housing 9630b side are The display area of the display unit 9631a and the display unit 9631b are substantially the same as each other. The display area of each of the 9631b is not particularly limited, and one size may be different from the other. The display quality may be different, e.g. one with higher resolution than the other. It may also be a display panel that can display
[0384] FIG. 28(B) shows the tablet terminal 9600 folded in half. The portable terminal 9600 includes a housing 9630, a solar cell 9633, and a DC-DC converter 9636. In addition, a charge and discharge control circuit 9634 including a power storage unit Such a power storage unit is used.
[0385] As mentioned above, the tablet terminal 9600 can be folded in half, so when not in use, The housing 9630a and the housing 9630b can be folded so as to overlap each other. By folding the tablet terminal 9600, the display portion 9631 can be protected, and thus the tablet terminal 9600 can be made durable. In addition, the power storage unit 9635 using the secondary battery of one embodiment of the present invention can A tablet that can be used for a long period of time due to its high capacity and good cycle characteristics. A mobile terminal 9600 can be provided.
[0386] In addition, a tablet terminal 9600 shown in FIG. 28(A) and FIG. 28(B) It has the function to display various information (still images, videos, text images, etc.), calendar, date Or a function to display the time, etc. on the display, and to operate or edit the information displayed on the display by touch input The touch input function, the function to control the processing by various software (programs), etc.
[0387] The tablet terminal 9600 is equipped with a solar cell 9633 on its surface, which provides power to the touch screen. The solar cell 96 can supply the power to the switch panel, the display unit, the image signal processing unit, etc. The power storage unit 9635 can be efficiently charged by the power storage unit 9635. The power storage unit 9635 may be a lithium-ion battery. The use of such a filter has the advantage of enabling miniaturization.
[0388] The configuration and operation of the charge / discharge control circuit 9634 shown in FIG. A block diagram is shown in FIG. 28C. 35, DC-DC converter 9636, converter 9637, switches SW1 to SW3, The display unit 9631 is shown, along with a storage battery 9635, a DC-DC converter 9636, and a The inverter 9637 and the switches SW1 to SW3 are connected to the charge / discharge control circuit 9 This corresponds to 634.
[0389] First, an example of operation in which power is generated by the solar cell 9633 using external light will be described. The power generated by the solar cell is converted to a voltage to charge the storage battery 9635. The converter 9636 increases or decreases the voltage. When power from the battery 9633 is used, the switch SW1 is turned on, and the converter 963 7, the voltage is increased or decreased to a voltage required for the display unit 9631. When not displaying in 1, turn SW1 off and SW2 on to turn on the power storage unit 9635. It is sufficient to configure the device so as to perform charging.
[0390] The solar cell 9633 is shown as an example of a power generating means, but is not limited thereto. Storage by other power generation means such as piezoelectric elements and thermoelectric conversion elements For example, the power may be transmitted and received wirelessly (contactlessly). The configuration is a non-contact power transmission module that charges the battery by connecting the battery to the battery, or by combining it with other charging means. You may do so.
[0391] Another example of electronic equipment is shown in FIG. 29. In FIG. 29, a display device 8000 is a display device according to the present invention. 8 is an example of an electronic device using a secondary battery 8004 according to one embodiment. 8000 corresponds to a display device for receiving TV broadcasts, and includes a housing 8001, a display unit 8002, a speaker, The secondary battery 8004 according to one embodiment of the present invention includes: The display device 8000 is provided inside a housing 8001. The display device 8000 is supplied with power from a commercial power source. It is also possible to use the power stored in the secondary battery 8004. Therefore, even when power cannot be supplied from a commercial power source due to a power outage or the like, the present invention according to one aspect of the present invention can be used. The display device 8000 can be used by using the secondary battery 8004 as an uninterruptible power source. become.
[0392] The display unit 8002 is a display device having a light emitting element such as a liquid crystal display device or an organic EL element in each pixel. Optical devices, electrophoretic displays, DMD (Digital Micromirror Devices) ice), PDP (Plasma Display Panel), FED (Field A semiconductor display device such as a 3D Emission Display can be used.
[0393] In addition, display devices are used for TV broadcast reception, personal computers, advertising displays, etc. This includes all display devices for displaying information, such as
[0394] In FIG. 29, a stationary lighting device 8100 includes a secondary battery 8 according to one embodiment of the present invention. 8101 is an example of an electronic device using the lighting device 8100. The device includes a light source 8102, a secondary battery 8103, and the like. In FIG. For example, the light source 101 and the light source 8102 are installed inside a ceiling 8104. 8, the secondary battery 8103 may be provided inside the housing 8101. The device 8100 can be supplied with power from a commercial power source or can be powered by a secondary battery 8103. The stored power can also be used. Therefore, in the event of a power outage, the supply of power from the commercial power source is not possible. Even when power is not available, the secondary battery 8103 according to one embodiment of the present invention can be used as an uninterruptible power source. This enables the lighting device 8100 to be used.
[0395] In addition, FIG. 29 illustrates a lighting device 8100 that is installed on a ceiling 8104. However, in the secondary battery according to one embodiment of the present invention, other than the ceiling 8104, for example, the side wall 8105, the floor The present invention can be applied to a lighting device installed in a fixed position such as a desk 8106 or a window 8107. It can also be used in upper lighting devices.
[0396] In addition, the light source 8102 can be an artificial light source that artificially obtains light using electricity. Specifically, this applies to incandescent lamps, discharge lamps such as fluorescent lamps, and light-emitting diodes and organic electroluminescence (EL) elements. An example of the artificial light source is a light element.
[0397] In FIG. 29, an air conditioner having an indoor unit 8200 and an outdoor unit 8204 is 8 is an example of an electronic device using a secondary battery 8203 according to one embodiment of the present invention. The indoor unit 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, and the like. In the example shown, the secondary battery 8203 is provided in the indoor unit 8200. The secondary battery 8203 may be provided in the outdoor unit 8204. The secondary battery 8203 may be provided in both the outdoor units 8204. The battery can be supplied with power from a commercial power source or can be charged by the power stored in the secondary battery 8203. In particular, both the indoor unit 8200 and the outdoor unit 8204 are equipped with secondary batteries 8 If 203 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. However, by using the secondary battery 8203 according to one embodiment of the present invention as an uninterruptible power supply, The use of conditioners will be possible.
[0398] In addition, Figure 29 shows a separate type air conditioner consisting of an indoor unit and an outdoor unit. However, an integrated air conditioner that has both the indoor and outdoor functions in a single housing is also shown. The secondary battery according to one embodiment of the present invention can also be used for the conditioner.
[0399] In FIG. 29, an electric refrigerator-freezer 8300 includes a secondary battery 8304 according to one embodiment of the present invention. Specifically, an electric refrigerator-freezer 8300 includes a housing 8301, The refrigerator door 8302, the freezer door 8303, the secondary battery 8304, and the like are included. A secondary battery 8304 is provided inside the housing 8301. The power can be supplied from a commercial power source, or the power stored in the secondary battery 8304 can be used. Therefore, when power cannot be supplied from commercial power sources due to a power outage, etc. Even in such a case, the secondary battery 8304 according to one embodiment of the present invention can be used as an uninterruptible power supply. It will be possible to use 8300 refrigerators / freezers.
[0400] Among the above-mentioned electronic devices, high-frequency heating devices such as microwave ovens and electric rice cookers The child devices require high power for a short period of time. Therefore, the power that cannot be supplied by the commercial power supply is supplemented. By using a secondary battery according to one embodiment of the present invention as an auxiliary power source for supporting This can prevent the commercial power breaker from tripping when using the device.
[0401] In addition, during periods when electronic devices are not in use, the total amount of power that can be supplied by commercial power suppliers is also During the time period when the ratio of the amount of electricity actually used (called the electricity usage rate) is low, By storing power in the secondary battery, it is possible to prevent the power usage rate from increasing outside the above time periods. For example, in the case of the electric refrigerator-freezer 8300, when the temperature is low, the refrigerator compartment door 83 02. During the night when the freezer door 8303 is not opened or closed, power is supplied to the secondary battery 8304. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 open and close. During the daytime, when the vehicle is turned on, the secondary battery 8304 is used as an auxiliary power source, so that the daytime power consumption is reduced. The rate can be kept low.
[0402] According to one embodiment of the present invention, the cycle characteristics of a secondary battery can be improved, and the reliability can be improved. Moreover, according to one aspect of the present invention, a high-capacity secondary battery can be obtained. This improves the characteristics of the secondary battery, thereby making the secondary battery itself smaller and lighter. For this reason, the secondary battery according to one embodiment of the present invention can be used in the electronic devices described in this embodiment. By mounting the electronic device in the above-mentioned embodiment, it is possible to obtain an electronic device with a longer life and a lighter weight. The embodiment can be implemented in appropriate combination with other embodiment modes.
[0403] (Embodiment 5) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle will be described.
[0404] When a secondary battery is installed in a vehicle, it becomes a hybrid vehicle (HEV), an electric vehicle (EV), or It will be possible to realize next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). do.
[0405] In FIG. 30(A), (B), and (C), a secondary battery according to one embodiment of the present invention is used. The vehicle 8400 shown in FIG. 30(A) uses electricity as a power source for running. It is an electric vehicle that uses a motor. Or, it uses an electric motor and The present invention relates to a hybrid vehicle that can use an engine selected as appropriate. By using this, it is possible to realize a vehicle with a long driving range. The secondary battery is attached to the floor of the vehicle interior as shown in FIG. 15(C) and FIG. 15(D). ) can be used by arranging the secondary battery modules shown in FIG. 18(A) and ( A battery pack consisting of multiple secondary batteries as shown in B) may be installed on the floor of the vehicle. The secondary battery not only drives the electric motor 8406, but also the headlights 8401 and the lamp Power can be provided to a light emitting device such as a room light (not shown).
[0406] In addition, the secondary battery is used for the displays of the car 8400 such as the speedometer and tachometer. The secondary battery can supply power to the navigation device of the automobile 8400. The present invention can provide power to semiconductor devices such as gating systems.
[0407] The automobile 8500 shown in FIG. 30(B) is a secondary battery that is plugged in to the automobile 8500. It is possible to charge the battery by receiving power from an external charging facility using a contactless charging method or other methods. FIG. 30(B) shows a case where a charging device mounted on a vehicle 8500 is connected to a ground-mounted charging device 8021. The secondary battery 8024 is shown being charged via a cable 8022. For charging methods and connector specifications, please refer to the specifications of CHAdeMO (registered trademark) and Combo. The charging device 8021 is a charging station installed in a commercial facility. For example, plug-in technology can be used to connect the power source to the outside. The secondary battery 8024 mounted on the automobile 8500 can be charged by the power supply. Charging is performed by converting AC power to DC power via a converter such as an AC / DC converter. It is possible to do so.
[0408] Although not shown, a power receiving device is mounted on the vehicle and receives power from a ground power transmitting device in a non-contact manner. In this case, the power transmission device is installed on the road or on the exterior wall. By incorporating this, charging can be done not only when the vehicle is stopped but also while the vehicle is moving. In addition, the vehicle exterior may be provided with a power supply. A solar cell may be provided in the vehicle so that the secondary battery can be charged when the vehicle is stopped or running. To supply power in the above, an electromagnetic induction method or a magnetic resonance method can be used.
[0409] FIG. 30C shows an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. The scooter 8600 shown in FIG. 1(C) includes a secondary battery 8602, side mirrors 8601, and a directional indicator. The secondary battery 8602 supplies electricity to the direction indicator light 8603. can be done.
[0410] In addition, the scooter 8600 shown in FIG. 30(C) has a secondary battery 86 in the storage space under the seat 8604. The secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 can be removed and stored in the under-seat storage 8604. When charging, the secondary battery 8602 is brought indoors, charged, and then stored away before driving. Just pay it.
[0411] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery is increased. Therefore, the secondary battery itself can be made smaller and lighter. If the vehicle itself can be made smaller and lighter, it will contribute to reducing the vehicle's weight, improving the vehicle's range. In addition, the secondary battery installed in the vehicle can be used as a power supply source for other purposes besides the vehicle. In this case, for example, it is possible to avoid using commercial power sources during peak power demand periods. If we can avoid using commercial power sources during peak power demand periods, we can save energy and This can contribute to reducing carbon dioxide emissions. In addition, if the cycle characteristics are good, Since the secondary battery can be used for a long period of time, the amount of rare metals used, including cobalt, can be reduced. It is possible.
[0412] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0413] In this example, a positive electrode active material containing magnesium, fluorine, and phosphorus was prepared. A secondary battery having a positive electrode using the active material was prepared, and the continuous charge durability and cycle The characteristics were evaluated.
[0414] <Preparation of positive electrode active material> The positive electrode active material was prepared by referring to the flows in FIGS. 8 and 9. Step S47 was not performed.
[0415] First, a mixture 902 containing magnesium and fluorine was prepared (steps shown in FIG. 8). Steps S11 to S14). The molar ratio of LiF and MgF2 is LiF:MgF2=1: The mixture was weighed out so that the total weight was 3, and acetone was added as a solvent, followed by wet mixing and grinding. The powder was crushed in a ball mill using zirconia balls at 150 rpm for 1 hour. The treated material was collected and designated mixture 902.
[0416] Next, a positive electrode active material containing cobalt was prepared (step S25). The lithium cobalt oxide synthesized for this purpose was CellSeed C-10 manufactured by Nippon Chemical Industry Co., Ltd. CellSeed C-10N is a cobalt alloy with a D50 of about 12 μm and few impurities. It is lithium oxide.
[0417] Next, the mixture 902 and lithium cobalt oxide were mixed (step S31). The atomic weight of magnesium in mixture 902 is compared to the atomic weight of cobalt in lithium tritate. The atomic weights were conditioned. The conditioned values were approximately 0.5%, 1.0%, 2.0%, and 3. The magnets of the positive electrode active materials were weighed out to be 0.0% and 6.0%. The atomic weight of sodium is shown in Tables 1 and 2 below. The mixture was dry mixed. The mixing was carried out in a ball mill using zirconia balls at 150 rpm for 1 hour.
[0418] Next, the treated material was collected to obtain a mixture 903 (steps S32 and S3 3).
[0419] Next, the mixture 903 was placed in an alumina crucible and heated at 850° C. for 6 h in a muffle furnace in an oxygen atmosphere. The alumina crucible was covered with a lid during the annealing. The oxygen flow rate was 10 L / min. The temperature rise rate was 200°C / hr, and the temperature drop rate was 10 hours or more. The material after the heat treatment is collected (step S35), sieved, and the magnesium oxide is removed. The positive electrode active material (positive electrode active material 100A_1 shown in FIG. 8) was prepared by adjusting the amount of ammonium added. The magnesium concentration was then calculated as 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21. 0.0% and 6.0% of the positive electrode active material 100A_1, respectively, 11. Sample 12. Sample 13. Samp These are called Sample 14 and Sample 15. The positive electrode active material 100A_1 obtained in this step and the positive electrode active material 100A_2 obtained in the following step were used for the preparation. The positive electrode active material subjected to steps S51 to S54, which will be described later, was used.
[0420] Thereafter, the metal addition in steps S42 to S47 shown in FIG. We then moved on to Step S51.
[0421] Next, lithium phosphate was prepared (step S51). The material 100A_1 was mixed (step S52). The amount of lithium phosphate mixed was The amount was equivalent to 0.06 mol per 1 mol of active material 100A_1. The mixture was mixed in a ball mill using ruthenium balls at 150 rpm for 1 hour. The mixture was then placed in an alumina crucible and covered with a lid. The resultant was annealed in an oxygen atmosphere at 750° C. for 20 hours (step S53). The powder was collected by sieving through a 1 mm diameter sieve (step S54). The positive electrode active material ( The following are positive magnesium concentrations: 0.5%, 1.0%, 2.0%, 3.0% and 6.0%. The active materials are Sample 21 and Sample 2, respectively. 2, Sample 23, Sample 24 and Samp le(sample) 25) was obtained.
[0422] <Preparation of secondary battery> Each positive electrode was prepared using each positive electrode active material obtained above. A slurry of AB and PVDF was prepared by mixing the active material, AB, and PVDF in a ratio of 95:3:2 (weight ratio). The slurry was coated on a current collector and NMP was used as the solvent for the slurry.
[0423] After the slurry was applied to the current collector, the solvent was evaporated. Then, a pressure of 210 kN / m was applied. After this, a pressure of 1467 kN / m was applied. Through these steps, a positive electrode was obtained. The loading on the electrode is approximately 20 mg / cm 2 It was decided.
[0424] Using the prepared positive electrode, a CR2032 type coin (diameter 20 mm, height 3.2 mm) was A secondary battery of this type was fabricated.
[0425] Lithium metal was used as the counter electrode.
[0426] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte used was ethylene carbonate (EC) and diethyl carbonate (DEC). The mixture was EC:DEC = 3:7 (volume ratio). For the secondary batteries that were tested, 2 wt% vinylene carbonate (VC) was added to the electrolyte. Ta.
[0427] The separator was made of polypropylene having a thickness of 25 μm.
[0428] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0429] <Continuous charging durability> Next, the continuous charge durability of each secondary battery using each of the prepared positive electrode active materials was evaluated. First, charging was performed under CCCV (0.05C, 4.5V or 4.6V, final current 0 0.005C), discharge CC (0.05C, 2.5V) for 2 cycles at 25℃ It was determined.
[0430] After that, charging was performed at 60°C with CCCV (0.05C). The upper limit voltage was 4.55V. or 4.65V, and the termination condition is when the secondary battery voltage is 0.01V below the upper limit voltage. The time it took for the voltage to drop below 4.54V (4.55V) was measured. If the voltage drops below the upper limit, a phenomenon such as a short circuit may have occurred. 1C was set to 200mA / g.
[0431] The measured time for each secondary battery is shown in Tables 1 and 2. Table 1 shows the steps The results are shown in Table 2, which is the result of using the positive electrode active material obtained in step S36. Positive electrode active material prepared through step S54, i.e., positive electrode active material to which a phosphorus compound has been added This is the result of using quality.
[0432] [Table 1]
[0433] [Table 2]
[0434] In addition, for the results using the positive electrode active material obtained in step S36, the charging voltage was set to 4.5 Figure 31(A) shows the time-current characteristics when the charging voltage is 5V, and Figure 31(B) shows the time-current characteristics when the charging voltage is 4.65V. The time-current characteristics are shown in FIG.
[0435] In addition, the positive electrode active material produced through steps S51 to S54, i.e., phosphorus The results of using the positive electrode active material to which the compound was added were as follows: the charging voltage was set to 4.55 V. The time-current characteristic when the charging voltage is set to 4.65 V is shown in Figure 32(A). The characteristics are shown in FIG.
[0436] By adding phosphorus compounds, the time until the voltage drop occurs is longer, and continuous charging is possible. Furthermore, when the Mg content was 2%, the continuous charging It was suggested that the resistance to electricity was significantly improved.
[0437] <Cycle characteristics> Next, the cycle characteristics of the secondary batteries using each of the positive electrode active materials were evaluated. First, the charge was CCCV (0.05C, 4.6V, final current 0.005C) and the discharge was CC (0.05C, 2.5V) was used for two cycles at 25°C. At ℃, charging is CCCV (0.2C, 4.6V, final current 0.02C), discharging is CC The battery was repeatedly charged and discharged at (0.2C, 2.5V) to evaluate the cycle characteristics.
[0438] In Figures 33(A) and (B), the horizontal axis indicates cycles, and the vertical axis indicates discharge capacity. This is the result of using the positive electrode active material obtained in step S36. The positive electrode active material prepared through steps S51 to S54, i.e., the addition of a phosphorus compound, These are the results of using the positive electrode active materials.
[0439] When we look at the rate of capacity loss versus the number of cycles, we see that the magnesium concentration has a significant effect. No difference can be seen. On the other hand, the higher the concentration of magnesium added, the greater the decrease in initial capacity. This is because the ratio of phosphorus compounds to the weight of the active material becomes high, This is thought to be because the proportion of cobalt decreases, decreasing the proportion of substances that contribute to charge and discharge reactions. . EXAMPLES
[0440] In this embodiment, magnesium, fluorine, cobalt, and metals other than cobalt are included. A positive electrode active material is prepared, a secondary battery having a positive electrode using the positive electrode active material is prepared, and XRD of the positive electrode after charging, continuous charging resistance of the secondary battery, and cycle characteristics of the secondary battery were evaluated. did.
[0441] <Preparation of positive electrode active material> Referring to the flow charts in FIG. 8 and FIG. 9, the positive electrode active material Sample 30 Sample 35 was produced in steps S51 to S55. S54 was not carried out.
[0442] First, regarding Sample 30 to Sample 35 A mixture 902 containing magnesium and fluorine was prepared (steps S11 to S15). LiF and MgF2 were weighed out so that the molar ratio of LiF:MgF2 was 1:3. The mixture was mixed and crushed in a wet manner using acetone as a solvent. The treatment was carried out in a ball mill using near balls at 150 rpm for 1 hour. The mixture was collected and named mixture 902.
[0443] Next, regarding Sample 30 to Sample 35 As a positive electrode active material containing cobalt, CellSeed C-10N manufactured by Nippon Chemical Industry Co., Ltd. was prepared (step S25).
[0444] Next, regarding Sample 30 to Sample 35 The mixture 902 and lithium cobalt oxide were mixed (step S31). The atomic weight of magnesium in mixture 902 compared to the atomic weight of cobalt in magnesium. The mixture was weighed out so that the content was 2.0%. The mixture was dry mixed. The mixture was mixed using zirconia balls. The grinding was carried out in a ball mill at 150 rpm for 1 hour.
[0445] Next, regarding Sample 30 to Sample 35 The treated material was collected to obtain a mixture 903 (steps S32 and S33). .
[0446] Next, regarding Sample 30 to Sample 35 The mixture 903 was placed in an alumina crucible and heated in a muffle furnace in an oxygen atmosphere at 850°C for 60 hours. The alumina crucible was covered with a lid during the annealing (step S34). The flow rate was 10 L / min. The temperature rise rate was 200°C / hr, and the temperature drop rate was 10 hours or more. The material after the heat treatment was collected and sieved (step S35), and the positive electrode active material 10 was obtained. 0A_1 was obtained (step S36).
[0447] Next, regarding Sample 31 to Sample 35 Then, the processes of steps S41 to S46 were performed. In the case of 30, the addition of the metal source in steps S41 to S46 was not performed. , Sample 31 to Sample 35, The positive electrode active material 100A_1 and the metal source were mixed by the step S41. The solvents were also mixed together.
[0448] <<Aluminum Addition>> For Sample 31 and Sample 32, A coating layer containing aluminum was formed on the positive electrode active material 100A_1 by a sol-gel method. The raw material used was Al isopropoxide, and the solvent used was 2-propanol. The atomic weight of aluminum is shown in Sample 31 for cobalt and aluminum. In Sample 32, the edge is The atomic weights of the titanium and aluminum were each adjusted to 0.5% of the total atomic weight. The mixture was then placed in an alumina crucible, covered, and heated in an oxygen atmosphere at 850°C. The powder was then sieved through a 53 μm φ sieve and annealed for 2 hours (step S45). The positive electrode active material was collected (step S46), and Samples 31 and S Ample (sample) 32 was obtained.
[0449] <<Nickel Addition>> For Sample 33 and Sample 34, Nickel hydroxide, which is a metal source, was mixed with the positive electrode active material 100A_1. In Sample 33, the atomic weight of cobalt and nickel is In Sample 34, the cobalt and nickel atoms are The mixture was mixed so that the total amount was 0.5%. The mixture was milled at 150 rpm for 1 hour in a ball mill. After mixing, the mixture was sieved through a 300 μm φ sieve. The mixture was then placed in an alumina crucible, covered with a lid, and heated in an oxygen atmosphere for 8 h. The mixture was annealed at 50° C. for 2 hours (step S45). Then, the mixture was sieved through a 53 μm φ sieve. The powder is collected (step S46) and used as a positive electrode active material as Sample 33. and Sample 34 was obtained.
[0450] <<Aluminum and nickel addition>> Sample 35 was made up of nickel hydroxide, which is the metal source, and Material 100A_1 is mixed with a ball mill, and then aluminum is added by the sol-gel method. The metal source was Al isopropoxide, and the solvent was 2 The atomic weights of nickel and aluminum were calculated using Co and Al, respectively. The total atomic weight of barium, nickel and aluminum is 0.5%. The mixture was then placed in an alumina crucible, covered with a lid, and heated in an oxygen atmosphere for 850 The mixture was annealed at 35° C. for 2 hours (step S45). After that, the mixture was sieved through a 53 μm φ sieve to separate the powder. was collected (step S46) to obtain Sample 35 as the positive electrode active material. .
[0451] <Preparation of secondary battery> Sample 30 to Sample 35 obtained above Each of the positive electrode active materials was used to prepare a positive electrode. F was mixed with active material, AB, and PVDF in a ratio of 95:3:2 (by weight) and the slurry was applied to the current collector. NMP was used as the solvent for the slurry.
[0452] After the slurry was applied to the current collector, the solvent was evaporated. Then, a pressure of 210 kN / m was applied. After this, a pressure of 1467 kN / m was applied. Through these steps, a positive electrode was obtained. The loading on the electrode is approximately 20 mg / cm 2 It was decided.
[0453] Using the prepared positive electrode, a CR2032 type coin (diameter 20 mm, height 3.2 mm) was A secondary battery of this type was fabricated.
[0454] Lithium metal was used as the counter electrode.
[0455] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte used was ethylene carbonate (EC) and diethyl carbonate (DEC). The mixture was EC:DEC = 3:7 (volume ratio). The secondary batteries tested had 2 wt% vinylene carbonate (VC) added to the electrolyte. did.
[0456] The separator was made of polypropylene having a thickness of 25 μm.
[0457] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0458] <XRD of positive electrode> First, before charging and discharging, the positive electrode was evaluated by XRD. shows the XRD of the positive electrode before charging and discharging. A prominent peak was observed at 5°. The horizontal axis of the graphs shown in Figures 34(A) and (B) is 2θ The vertical axis is intensity.
[0459] <XRD of positive electrode after charging> Next, the fabricated secondary batteries were charged to 4.55 V, 4.6 V, 4.65 V, and 4.7 V. V was selected for each condition. After constant current charging at 0.2C, the battery was charged at a constant voltage until the current reached 0.02C. The charge current was set to 191mA / g for 1C. The secondary battery in the charged state was placed in a globe with an argon atmosphere. The box is disassembled, the positive electrode is removed, and it is washed with DMC (dimethyl carbonate) and electrolyzed. The liquid was removed, and the mixture was placed in a sealed container under an argon atmosphere and subjected to XRD analysis.
[0460] Figures 35(A) and (B) show the results for Sample 35, respectively. The horizontal axis of the graphs shown in Figures 35(A) and (B) shows the XRD corresponding to the charging voltage conditions. is 2θ, and the vertical axis is Intensity.
[0461] Figure 35(A) shows the peaks observed in the 2θ range from 18° to 20°. The peak observed at 4.55 V is thought to be due to the O3 type crystal structure. As the voltage increases, the peak position moves to the higher angle side. In this case, in addition to the peak near 18.9°, a peak was also observed near 19.2°. In the two-phase mixture state, the crystal structure is O3 type and the pseudospinel type. This suggests that the temperature is around 19.3° when the charging voltage is 4.7 V. The peak is believed to be due to a pseudospinel type crystal structure.
[0462] Figure 35(B) shows the peaks observed in the 2θ range from 40° to 50°. As the temperature rises, a peak appears at 43.9°, suggesting an H1-3 crystal structure, at 4.7 V. The peak becomes weaker and can be observed.
[0463] As described above, in the positive electrode active material of one embodiment of the present invention, as the charging voltage is increased, At 5V, it is believed that a region occurs where the O3 crystal structure changes to a pseudospinel crystal structure. Even at a voltage of 4.7 V, the H1-3 crystal structure was still present, but the pseudo-single crystal structure was predominant. The positive electrode active material of one embodiment of the present invention is considered to have a Pinel type crystal structure and has a high charging voltage. It was also suggested that the compound was highly stable even in
[0464] <Continuous charging durability> Next, the continuous charging durability of the secondary battery was evaluated. Secondary batteries using Samples 0 to 35 as positive electrode active materials, Charge with CCCV (0.05C, 4.5V or 4.6V, final current 0.005C), discharge was measured for two cycles at 25° C. under CC (0.05 C, 2.5 V).
[0465] After that, charging was performed at 60°C with CCCV (0.05C). The upper limit voltage was 4.55V. or 4.65V, and the termination condition is when the secondary battery voltage is 0.01V below the upper limit voltage. The time it took for the voltage to drop below 4.54V (4.55V) was measured. If the voltage drops below the upper limit, a phenomenon such as a short circuit may have occurred. . 1C was set to 200mA / g.
[0466] The measured time for each secondary battery is shown in Table 3. Duplicate batteries were fabricated, and Table 3 shows the average of the two results.
[0467] [Table 3]
[0468] Also Sample 30, Sample 32, Sample The results using Sample 34 and Sample 35 were Figure 36(A) shows the time-current characteristics when the charging voltage is 4.55 V, and The time-current characteristics for V are shown in FIG.
[0469] By adding aluminum, the time until the voltage drop occurs is longer, and continuous charging is possible. It was also suggested that the resistance of nickel was improved compared to the case where only nickel was added. The addition of zinc and aluminum significantly improved the durability against continuous charging. Ta.
[0470] <Cycle characteristics> Next, Sample 30, Sample 32, Samp Regarding the secondary battery using Sample 34 and Sample 35 The cycle characteristics were evaluated using CCCV (0.05C, 4.6V, final charge Current 0.005C) and discharge CC (0.05C, 2.5V) at 25°C for 2 cycles. After that, charging was performed at 25°C under CCCV (0.2C, 4.6V, final current The battery was repeatedly charged and discharged at CC (0.02C, 2.5V) and discharged at CC (0.2C, 2.5V). The sex was evaluated.
[0471] The results of the cycle characteristics are shown in Figure 37. In Figure 37, the horizontal axis indicates the cycle and the vertical axis indicates the discharge capacity. Also, in Figure 38(A) there is Sample 32, and in Figure 38(B) there is Samp Figure 38(C) shows the first charge of Sample 34 and Sample 35. The discharge curve shows that the initial capacity improved due to the addition of nickel (Sample 34) In addition, the addition of nickel or aluminum reduces the amount of oxidation that occurs with each cycle. It was suggested that the capacity loss due to the addition of nickel and aluminum was suppressed. Better results were obtained in (Sample 35). EXAMPLES
[0472] In this example, the positive electrode was evaluated by measuring the DC resistance.
[0473] <Preparation of secondary battery> A positive electrode was prepared using Sample 11 shown in Example 1 as a positive electrode active material. The positive electrode active material, carbon black and PVDF were mixed. The slurry was mixed with DF = 90:5:5 (weight ratio) and coated on the current collector. NMP was used as the solvent for the slurry.
[0474] After the slurry was applied to the current collector, the solvent was evaporated. Then, a pressure of 210 kN / m was applied. After this, a pressure of 1467 kN / m was applied. Through these steps, a positive electrode was obtained. The loading on the electrode is approximately 20 mg / cm 2 It was decided.
[0475] Using the prepared positive electrode, a CR2032 type coin (diameter 20 mm, height 3.2 mm) was A secondary battery of this type was fabricated.
[0476] Lithium metal was used as the counter electrode.
[0477] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluorophosphate (LiPF6). The electrolyte used was ethylene carbonate (EC) and diethyl carbonate (DEC). The mixture was EC:DEC = 3:7 (volume ratio). For the secondary batteries that were tested, 2 wt% vinylene carbonate (VC) was added to the electrolyte. Ta.
[0478] The separator was made of polypropylene having a thickness of 25 μm.
[0479] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0480] <Charge / discharge cycle test> DC resistance was measured before and after 50 charge / discharge cycle tests. The charge-discharge cycle test was carried out under the conditions shown in Example 1.
[0481] <DC resistance measurement> Next, the DC resistance was measured using the secondary battery. The system used was HJ1001SM8A type from Hokuto Denko Corporation.
[0482] First, the battery was charged to 4.5 V at 25°C using CCCV, and then rested for 20 minutes. After the CC discharge was performed to 3.0 V, the battery was left to rest for 20 minutes. The discharge capacity obtained by the measurement was Using this as a reference, DC resistance measurements were performed under various SOC conditions as follows.
[0483] First, the battery was charged to 4.5 V by CCCV at 25°C. Then, it was discharged and S DC resistance measurements were taken at three OC conditions: 70%, 20%, and 10%. went.
[0484] At each SOC, current is applied for a certain period of time after the discharge capacity reaches a certain SOC. The DC resistance was measured and is shown in Table 4.
[0485]
Table 4
[0486] The smaller the SOC, the greater the tendency for the DC resistance to increase. Also, after performing the cycle test, the DC resistance was found to increase by about 1.3 to 1.4 times.
Example
[0487] In this example, cross-sectional TEM-EDX analysis of the particles of the positive electrode active material according to one aspect of the present invention was performed.
[0488] After thinning each sample by FIB (Focused Ion Beam System: focused ion beam processing observation device), a TEM image was observed. FIG. 39(A) shows a cross-sectional TEM image of Sample 35 prepared in Example 2.
[0489] <TEM-EDX Analysis> In FIG. 39(A), TEM-EDX analysis was performed on the portion surrounded by the broken line. The analysis was performed linearly from the surface to the inside of the particle. The line was made approximately perpendicular to the surface. FIG. 39(B) shows the results of the line analysis of EDX. In the vicinity of the surface, relatively, the concentration of aluminum tended to be high and the concentration of cobalt tended to be low. Also, an increase in the concentration of magnesium was suggested near the surface. From this, in the particles of the positive electrode active material, it is possible that aluminum, magnesium, etc. contribute to the stabilization of the structure on the particle surface.
Example
[0490] In this example, a secondary battery including a positive electrode using the positive electrode active material of one embodiment of the present invention was manufactured. The positive electrode of the secondary battery was evaluated by XRD after charging.
[0491] Sample 30 and Sample 3 prepared in Example 2 35 to prepare positive electrodes, and then use each of the positive electrodes to prepare secondary batteries. The positive electrode and the secondary battery were produced by the methods shown in Example 2.
[0492] <XRD of positive electrode after charging> Next, each secondary battery was selected to be 4.6V or 4.65V. CCV charging was performed. Specifically, at 45°C, the battery was charged at a constant current of 0.2C up to each voltage, and then The battery was charged at a constant voltage until the current reached 0.02 C. Here, 1 C corresponds to 191 mA / g. The charged secondary battery was then disassembled in an argon atmosphere glove box to remove the positive electrode. The electrodes were then taken out and washed with DMC (dimethyl carbonate) to remove the electrolyte. The mixture was placed in a sealed container with a PO atmosphere and subjected to XRD analysis.
[0493] Figure 40 (A) and (B) show the results of XRD. In sample 30, in addition to the peak suggesting the H1-3 type crystal structure, The peaks around 20.9° and 36.8° are clearly observed. The peak next to it is suggested to be due to CoO2, and lithium is released, causing the crystal structure to collapse. In contrast, in Sample 35, the pseudo-stable state A pinel structure was suggested, and it was also suggested that the material is stable even at high charging voltages. [Explanation of symbols]
[0494] 100: Positive electrode active material, 100A: Positive electrode active material, 100A_1: Positive electrode active material, 100A_2 : Positive electrode active material, 100A_3: Positive electrode active material, 100C: Positive electrode active material, 200: Active material layer, 201: graphene compound, 211a: positive electrode, 211b: negative electrode, 212a: lead, 21 2b: lead, 214: separator, 215a: joint, 215b: joint, 217: fastener Fixing member, 250: secondary battery, 251: exterior body, 261: bent portion, 262: seal portion, 263: seal portion, 271: ridge line, 272: valley line, 273: space, 300: secondary battery, 3 01: Positive electrode can, 302: Negative electrode can, 303: Gasket, 304: Positive electrode, 305: Positive electrode current collector body, 306: positive electrode active material layer, 307: negative electrode, 308: negative electrode current collector, 309: negative electrode active material layer 310: separator, 500: secondary battery, 501: positive electrode current collector, 502: positive electrode active material layer , 503: positive electrode, 504: negative electrode current collector, 505: negative electrode active material layer, 506: negative electrode, 507: Separator, 508: electrolyte, 509: exterior body, 510: positive electrode lead electrode, 511: negative electrode Lead electrode, 600: secondary battery, 601: positive electrode cap, 602: battery can, 603: positive electrode Terminal, 604: positive electrode, 605: separator, 606: negative electrode, 607: negative electrode terminal, 608: Insulating plate, 609: insulating plate, 611: PTC element, 612: safety valve mechanism, 613: conductive plate, 614: Conductive plate, 615: Module, 616: Conductive wire, 617: Temperature control device, 900: circuit board, 901: raw material, 902: mixture, 903: mixture, 904: mixture, 910: Label, 911: terminal, 912: circuit, 913: secondary battery, 914: antenna, 916: Layer, 917: layer, 918: antenna, 920: display device, 921: sensor, 922: terminal , 930: housing, 930a: housing, 930b: housing, 931: negative electrode, 932: positive electrode, 93 3: separator, 950: winding body, 951: terminal, 952: terminal, 980: secondary battery, 9 81: film, 982: film, 993: winding body, 994: negative electrode, 995: positive electrode, 9 96: separator, 997: lead electrode, 998: lead electrode, 7100: portable display device , 7101: housing, 7102: display unit, 7103: operation button, 7104: secondary battery, 7 200: Portable information terminal, 7201: Housing, 7202: Display unit, 7203: Band, 720 4: Buckle, 7205: Operation button, 7206: Input / output terminal, 7207: Icon, 7 300: display device, 7304: display unit, 7400: mobile phone, 7401: housing, 740 2: display unit, 7403: operation buttons, 7404: external connection port, 7405: speaker, 7406: Microphone, 7407: Secondary battery, 7500: Electronic cigarette, 7501: Atomizer , 7502: cartridge, 7504: secondary battery, 8000: display device, 8001: housing 8002: display unit, 8003: speaker unit, 8004: secondary battery, 8021: charging device , 8022: cable, 8024: secondary battery, 8100: lighting device, 8101: housing, 8 102: Light source, 8103: Secondary battery, 8104: Ceiling, 8105: Side wall, 8106: Floor, 8107: Window, 8200: Indoor unit, 8201: Housing, 8202: Air outlet, 8203: Secondary Battery, 8204: Outdoor unit, 8300: Electric refrigerator / freezer, 8301: Housing, 8302: Refrigeration room door, 8303: freezer door, 8304: secondary battery, 8400: automobile, 8401: headlight, 8406: electric motor, 8500: automobile, 8600: scooter, 860 1: Side mirror, 8602: Secondary battery, 8603: Turn signal light, 8604: Under-seat storage , 9600: Tablet terminal, 9625: Switch, 9627: Switch, 9628: Operation switch, 9629: fastener, 9630: housing, 9630a: housing, 9630b: housing body, 9631: display section, 9631a: display section, 9631b: display section, 9633: solar cell , 9634: charge / discharge control circuit, 9635: power storage body, 9636: DCDC converter, 96 37: Converter, 9640: Moving part
Claims
1. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, the positive electrode active material particles having a depth of charge of 0.7 or more and 0.9 or less have a crystal structure of space group R-3m, in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25); a surface layer portion of the positive electrode active material particle having the fluorine in a region in contact with the electrolyte solution;
2. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 1 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
3. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 0.5 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
4. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion of the positive electrode active material particle and the crystal defects or their vicinity contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
5. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion of the positive electrode active material particle and the crystal defects or their vicinity contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, the positive electrode active material particles having a depth of charge of 0.7 or more and 0.9 or less have a crystal structure of space group R-3m, in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25); a surface layer portion of the positive electrode active material particle having the fluorine in a region in contact with the electrolyte solution;
6. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion of the positive electrode active material particle and the crystal defects or their vicinity contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 1 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
7. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion of the positive electrode active material particle and the crystal defects or their vicinity contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 0.5 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
8. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion and the grain boundary or the vicinity thereof of the positive electrode active material particle contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
9. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion and the grain boundary or the vicinity thereof of the positive electrode active material particle contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, the positive electrode active material particles having a depth of charge of 0.7 or more and 0.9 or less have a crystal structure of space group R-3m, in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25); a surface layer portion of the positive electrode active material particle having the fluorine in a region in contact with the electrolyte solution;
10. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion and the grain boundary or the vicinity thereof of the positive electrode active material particle contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 1 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
11. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, the surface layer portion and the grain boundary or the vicinity thereof of the positive electrode active material particle contain magnesium, fluorine, nickel and aluminum; the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 0.5 nm from the surface of the positive electrode active material particles, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
12. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, A part of the surface layer has a rock salt type crystal structure, the positive electrode active material particles further have a layered rock-salt type crystal structure whose crystal orientation generally coincides with that of the rock-salt type crystal structure, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
13. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX ray analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, a surface layer portion of the positive electrode active material particle has the fluorine in a region in contact with the electrolyte, A part of the surface layer has a rock salt type crystal structure, the positive electrode active material particles further have a layered rock-salt type crystal structure whose crystal orientation generally coincides with that of the rock-salt type crystal structure, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
14. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 1 nm from the surface of the positive electrode active material particles, A part of the surface layer has a rock salt type crystal structure, the positive electrode active material particles further have a layered rock-salt type crystal structure whose crystal orientation generally coincides with that of the rock-salt type crystal structure, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
15. A lithium ion secondary battery having a positive electrode, a negative electrode, and an electrolyte, The positive electrode has positive electrode active material particles having lithium cobalt oxide, a surface layer portion of the positive electrode active material particle contains magnesium, fluorine, nickel and aluminum, the magnesium concentration in the surface layer portion is higher than the magnesium concentration in the interior of the positive electrode active material particle, In EDX analysis of the positive electrode active material particles, the aluminum concentration peak is in a deeper region than the magnesium concentration peak, In EDX analysis of the positive electrode active material particles, a fluorine concentration peak exists at a depth of 0.5 nm from the surface of the positive electrode active material particles, A part of the surface layer has a rock salt type crystal structure, the positive electrode active material particles further have a layered rock-salt type crystal structure whose crystal orientation generally coincides with that of the rock-salt type crystal structure, The positive electrode active material particles having a depth of charge of 0.7 to 0.9 are in a space group R-3m, and have a crystal structure in which the coordinates of cobalt in a unit cell are represented by (0,0,0.5) and the coordinates of oxygen are represented by (0,0,x) (where 0.20≦x≦0.25).
16. In any one of claims 1 to 15, The surface layer further contains cobalt.
17. In any one of claims 1 to 16, The surface layer portion is a region extending from the surface of the positive electrode active material particle to a depth of 10 nm.
18. In any one of claims 1 to 17, A lithium ion secondary battery, wherein when a coin-type secondary battery prepared using lithium metal for the positive electrode and counter electrode is charged to 4.7 V by CCCV charging and then the positive electrode removed from the coin-type secondary battery is analyzed by powder X-ray diffraction using CuKα1 radiation, the XRD pattern has diffraction peaks at least at 2θ = 19.30 ± 0.20° and 2θ = 45.55 ± 0.10°.
19. In any one of claims 1 to 17, A lithium ion secondary battery, wherein when a coin-type secondary battery prepared using lithium metal for the positive electrode and counter electrode is charged to 4.65 V by CCCV charging and then the positive electrode removed from the coin-type secondary battery is analyzed by powder X-ray diffraction using CuKα1 radiation, the XRD pattern has diffraction peaks at least at 2θ = 19.30 ± 0.20° and 2θ = 45.55 ± 0.10°.
20. In claim 18 or 19, The CCCV charging is a lithium-ion secondary battery in which the battery is charged at a constant current of 0.2 C (where 1 C is 191 mA / g) at 25° C., and then charged at a constant voltage until the current value reaches 0.02 C.
21. In any one of claims 18 to 20, A lithium ion secondary battery, wherein when the XRD pattern is analyzed by the Rietveld method, the proportion of the pseudo-spinel crystal structure is 50 wt % or more.
22. 22. In claim 21, The positive electrode has an O3 type crystal structure before the charging, the positive electrode has the pseudo-spinel crystal structure and an H1-3 crystal structure after the charging,
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and method for manufacturing the same
JP2002216760A
Positive electrode active material for lithium secondary battery and its manufacturing method
JP2006261132A
Lithium ion secondary battery positive electrode material, and lithium ion secondary battery positive electrode and lithium ion secondary battery using the same
JP2017188466A
Cathode active material, manufacture method of cathode active material, and secondary battery
JP2018088400A
Positive electrode active material particle and manufacturing method of positive electrode active material particle
US20180102536A1